Grain boundary engineering
Patent Information
- Application Number
- JP2024201319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2015-06-17
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-05
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025028905000001_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application is a continuation of U.S. Provisional Patent Application No. 62 / 037,754, filed August 15, 2014, and U.S. Provisional Patent Application No. 62 / 037,754, filed June 15, 2015. This application claims priority to U.S. nonprovisional patent application Ser. No. 14 / 742,080, filed on the 17th, It is incorporated herein by reference. [Background technology]
[0002] (background) The present disclosure relates to the fabrication of neodymium-iron-boron (Nd-Fe-B) sintered magnets using grain boundary engineering (GBE). Concerning construction.
[0003] The global market for rare earth permanent magnets (REPM) is growing along with the range of applications for REPM. They exhibit high magnetic performance characteristics and are used in a wide range of applications including electronics, energy, transportation, aerospace, defense, medical equipment, It is used in the development of advanced technology applications and high-efficiency applications in many industries, including information and communication technology. do.
[0004] For example, applications using Nd-Fe-B permanent magnets include: starter motors, antilock Braking system (ABS), fuel pump, blower, loudspeaker, microphone Switches, relays, hard disk drives (HDD), stepping Motors, servo motors, magnetic resonance imaging (MRI), wind turbine generators, robotics, Examples include sensors, magnetic separation devices, guidance systems, satellites, and cruise missiles.
[0005] Nd-Fe-B type sintered magnets have a highly finely tuned elemental composition, which includes, in addition to Nd, Examples of suitable transition metal elements include Dy, Tb, Ga, Co, Cu, Al and other small amounts of transition metal element additions.
[0006] The use of dysprosium (Dy), a heavy rare earth, helps improve the temperature resistance of Nd-Fe-B magnets. Although dysprosium has properties that improve performance, its resources are limited. The supply risk and scarcity of Dy limits the availability of high-temperature alloys for use in energy-saving motor applications. This has caused a shortage of high performance Nd-Fe-B magnets.
[0007] The present disclosure of grain boundary engineering maintains high performance, improves temperature resistance, and reduces production costs. The Dy content in Nd-Fe-B products is reduced while decreasing the Cr content. Summary of the Invention
[0008] (overview) The process can be used to determine, for example, particle size, alignment, density, energy product (BHmax), remanence, Nd2Fe with specific performance characteristics such as a desired combination of magnetic field strength (Br) and coercivity (iHc). 14 B-ei For example, the grain boundary engineering (GBE) process can include the creation of grain boundary modified rich magnets. The GBE process can include the production of new magnetic materials, e.g. Nd-Fe-B permanent magnets with various phases. For example, recycled magnetic materials, from those never used before in consumer products, For example, new magnets may be sourced from those previously used in consumer products, or from both. It can be made.
[0009] The GBE process maintains the original grain phase of the starting magnetic material, but modifies the grain boundary phase of the starting magnetic material. For example, the new Nd2Fe 14 When producing B magnets, the GBE system In the GBE system, at least 90 vol% of the Nd-Fe-B 2:14:1 phase grains from the starting material are retained. The system replaces all or substantially all of the Nd-rich grain boundary phase with a new phase made from additive material. In some instances, the GBE system may be able to replace the grain boundary phase in the final magnetic product. In some examples, the GBE system maintains about 3 to about 1% by volume of the starting grain. The 2 vol% Nd-rich grain boundary phase is replaced with a new grain boundary phase.
[0010] In general, one innovative aspect of the subject matter described herein is to melt a magnetic element and forming a cast alloy flake from the molten alloy, the cast alloy flake comprising a plurality of 2:14:1 phase grains; while maintaining at least a portion of the 2:14:1 phase grains from the cast alloy flake. crushing the cast alloy flakes to produce a first powder; pressing particles in the first powder. and aligning to form a first compact; sintering the first compact. forming a sintered compact; and removing at least a portion of the 2:14:1 phase grains from the sintered compact. while maintaining the sintered compact in a state where the sintered compact is fragmented to form a second powder; and mixing the second powder with at least one of the first and second powders while maintaining at least a portion of the original 2:14:1 phase grains, the second powder being: a) i) Nd, ii) iii) Pr, or iv) Dy. material R, and b) at least one, at least two of i) Co, ii) Cu, or iii) Fe, or mixing said additive A with an elemental additive B containing all three of said additives to produce a homogeneous powder; and sintering and magnetizing the powder to form a Nd-Fe-B magnetic article. Other embodiments of this aspect include: A corresponding computer system, apparatus, or one or more computer storage devices This includes computer programs recorded on the system. software, firmware, or hardware that, when activated, causes the system to perform said actions , or a combination thereof, to identify one or more computer systems. When executed by a data processing device, the data processing device can be configured to perform the following operations or actions: , by including instructions that cause the device to perform the actions described above, Programs can be configured to perform particular operations or actions.
[0011] Each of the above and other embodiments may optionally include one or more of the following features: The molten alloy may include, singly or in combination, a plurality of 2:14:1 phase grains. Forming cast alloy flakes from the molten alloy includes forming cast alloy flakes each of which includes a plurality of 2:14:1 phase grains. The rare earth material R and the elemental additive A may be formed into a cast alloy flake. As, Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 It can be at%.
[0012] In some embodiments, fragmenting the sintered compact comprises fragmenting the sintered compact into 1 to 4 pieces. The method includes: fragmenting the sintered compact to an average particle size of 100 microns. The forming of the second powder includes forming a second powder from the second powder. and removing particles having a particle fraction size larger than the particle size, and reducing the oxygen concentration to less than 1.98 at. The sintered compact may be fragmented to obtain the second powder. The powder is formed by fragmenting the sintered compact into particles having an average size of about 1 micron to about 2 millimeters. forming the second powder having a uniform particle size, the method comprising: and further fragmenting the second powder to an average particle size of about 1 to about 4 microns. Homogenizing the second powder includes homogenizing the second powder to a size of about 1 micron to about 2 millimeters. and homogenizing the second powder having an average particle size of about 100 μm, and a) said rare earth material R and b) said elemental additive A, to form said homogenous powder. a) mixing the second powder having an average particle size of about 1 to about 4 microns with the rare earth material R and and b) mixing said second additive with said elemental additive A to form said homogenous powder. mixing the powder with a) the rare earth material R and b) the elemental additive A to form the homogenous powder; forming a second powder having an average particle size of about 1 micron to about 2 millimeters; a) mixing said rare earth material R and b) said elemental additive A to form said homogenous powder. homogenizing the second powder may include homogenizing the second powder to a powder having an average particle size of about 1 to about 4 microns. The method may include homogenizing the second powder.
[0013] In some implementations, the sintered compact is fragmented to form the second powder. Separately, the rare earth material R and the elemental additive A are fragmented, where the second powder is a) said rare earth material R and b) said elemental additive A to form said homogenous powder. The second powder is then divided into a fractionated rare earth material R and a fractionated element additive R. The Nd-Fe-B magnetic product is mixed with the substance A to produce the homogeneous powder. The atomic percentage of Cu in the Nd-Fe-B magnetic product may be 3.098 at% or less. The combined atomic percentage of Fe and Co in the Nd-Fe-B magnetic product may be 0.1849 at% or less. The total Fe and Co in the Nd-Fe-B magnetic product may be about 76.3928 to about 83.1267 at %. The combined atomic percentage of Nd, Pr, and D in the Nd-Fe-B magnetic product may be 77 at% or less. The total atomic percentage of y is equal to or less than the total atomic percentage of Nd, Pr, and Dy in the sintered compact. The combined atomic percentage of Nd, Dy, and Pr in the Nd-Fe-B magnetic product may be 18a or more. It can be t% or less.
[0014] In some implementations, the second powder is made of a) the rare earth material R and b) the elemental additive. mixing the rare earth material R with the second powder to form the homogenous powder; and uniformly distributing the elemental additive A. Sintering and magnetizing the homogeneous powder to obtain a product. forming the Nd—Fe—B magnetic product, on average, in the Nd—Fe—B magnetic product 14:1 having an increasing concentration of the rare earth material R and an increasing concentration of the elemental additive A surrounding the phase grains. forming the Nd—Fe—B magnetic article from the sintered compact. The old Nd-rich grain boundary phase contained in the second powder is mixed with the rare earth material R and the element additive A. With a new grain boundary phase comprising
[0015] In some implementations, the Nd—Fe—B magnetic product has a molecular weight of [7.3635, 11.1038] (at%, both Nd, the quantity in the range [76.3928,80.0287] (at%, inclusive) Fe in the amount of 0.001% and B in the amount of 0.001% in the range [5.7493, 6.4244] (at%, inclusive). The Nd-Fe-B magnetic product contains O in an amount ranging from [0.09, 4.0] (at%, inclusive), and The Nd-Fe-B magnetic alloy may contain C in an amount ranging from [0.01, 1.0] (at %), both values being inclusive. The product may contain Dy in an amount in the range of [0.199, 4.0535] (at%, inclusive). d-Fe-B magnetic products contain Pr in amounts ranging from [1.445, 3.6323] (at%, inclusive). The Nd-Fe-B magnetic product may be prepared in an amount ranging from [0, 3.098] (at %, inclusive). The Nd-Fe-B magnetic product may contain Co of [0.0508, 0.1849] (at%, inclusive). The total amount of rare earth material R in the Nd—Fe—B magnetic article may include an amount of Cu ranging from about 100 to about 1000 μm. The range may be [12.66,15.03] (at%, inclusive).
[0016] In some implementations, the rare earth material R has a concentration of: i) [6.1717, 11.8917] (at%, both ends ii) the amount of Nd in the range [1.5495,4.821] (at%, inclusive) or iii) an amount of Dy in the range of [0.2132, 5.3753] (at%, inclusive). and the element additive A includes at least one of the following: i) [0, 4.0948] (at%, both ends of the value ii) an amount of Co in the range [0.0545,0.2445] (at%, inclusive); of Cu, or iii) Fe in the range of [81.1749, 85.867] (at%, inclusive). These ranges relate only to the rare earth material R and the elemental additive A. The starting magnet material, whether it is virgin or discarded magnet material, It is not about sexual material.
[0017] In some implementations, the homogenous powder is sintered and magnetized to form a Nd-Fe-B magnetic article. The homogeneous powder is sintered and magnetized to obtain a sintered molded product having a remanent magnetism and a coercive force. forming said Nd-Fe-B magnetic article at least equal to said body. The coercive force of the product may be about 0 to about 20% greater than the coercive force of the sintered compact. Sintering and magnetizing the homogeneous powder to form a Nd-Fe-B magnetic product is The sintered compact is sintered and magnetized to obtain a final remanence which is about 97% of the original remanence of the sintered compact, and the sintered compact is magnetized to obtain a final remanence which is about 97% of the original remanence of the sintered compact. The Nd-Fe-B magnetic body has a final coercivity that is at least 30% greater than the coercivity of the remaining sintered body. sintering and magnetizing the homogenous powder to form a Nd-Fe-B magnetic article. Forming the article comprises sintering and magnetizing the homogeneous powder to remove any residual magnetism from the sintered compact. A final remanence that is about 95% of the original magnetic remanence, and at least 80% greater than the original magnetic remanence of the sintered compact. forming said Nd-Fe-B magnetic article having a final coercivity of 0.15 or less. Sintering and magnetizing the powder to form the Nd-Fe-B magnetic product is a process for sintering and magnetizing the homogeneous powder. and magnetizing the sintered compact to obtain a final remanence that is about 5% greater than the other remanences of the sintered compact, and The Nd-Fe-B magnetic article is formed having a final coercivity at least equal to the other coercivity of the sintered body. This may include forming a
[0018] In general, one innovative aspect of the subject matter described herein is a method for producing Nd 1-20 Dy 1-60 Co 1-60 Cu 0.1 -20 Fe 0.5-90 The compound may be embodied as a compound containing Nd 7-14 Dy 30- 50 Co 28-45 Cu 1-10 Fe 1-10 The compound may be Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 The compound may be Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 It can be at% The compound may contain less than 0.12 at % oxygen, less than 0.0058 at % carbon, or both. In some examples, the compound contains 0.00009 to 0.18 at % oxygen, or 0.028 to 0.1 at % acid. In some examples, the compound may contain 0.0001 to 0.09 at % carbon, or 0.00 It may contain 58 to 0.009 at% carbon.
[0019] In some implementations, the compound may consist essentially of the depicted formula. For example, the compound essentially consists of Nd 1-20 Dy 1-60 Co 1-60 Cu 0.1-20 Fe 0.5-90 at%, Nd 7-14 Dy 30-50 Co 28-45 Cu 1-10 Fe 1-10 at%, Nd 8.5-12.5 Dy 35-45 Co 32-41Cu 3-6.5 Fe 1.5-5 at%, or Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The compound may be composed of 0.12 at%. % oxygen, less than 0.0058 at % carbon, or both. The mixture may contain 0.00009 to 0.18 at % oxygen, or 0.028 to 0.1 at % oxygen. In some examples, the compound contains 0.0001 to 0.09 at % carbon, or 0.0058 to 0.009 at % carbon. It can be seen.
[0020] In general, one innovative aspect of the subject matter described herein is: i) [6.1717, 11.8917]( ii) the amount of Nd in the range [1.5495,4.821] (at%, inclusive); or iii) an amount of Pr in the range [0.2132, 5.3753] (at%, inclusive). At least one of the quantities Dy and Dy in the range [0, 4.0948] (at%, inclusive) Co in an amount ranging from [0.0545,0.2445] (at%, inclusive), Cu in an amount ranging from [81.1749 ,85.867] (at%, inclusive) The compound contains Nd, Pr, and The compound may include a combination of Nd and Dy. The compound may include at least both Nd and Dy. may contain at least both Nd and Pr. The compound may contain Nd. The compound may contain 0. The compound may contain 0.028 to 0.1 at % of oxygen (O). The compound may contain 0.0001 to 0.09 at % of carbon (C). The compound may contain 0.0058 to 0 It may contain .009at% carbon (C).
[0021] In general, one innovative aspect of the subject matter described herein is the synthesis of a ferroelectric material comprising Cu, Co, and Fe, and N. The act of melting one or more of D, Pr, Dy, or Tb to prepare a molten alloy, and The method may be embodied in a method that includes cooling the alloy to produce a cast alloy flake. Another embodiment of this aspect is a pair of devices, each configured to perform the actions of the method. Corresponding computer systems, devices, and one or more computer storage devices The computer program installed on the system and executing the program on the system. Any software, firmware, hardware, or other device that causes the system to perform the actions described above. By having these combinations, one or more computer systems can be operated or The method is configurable to perform an action when executed by a data processing device. The one or more computer programs may be included in the device to include instructions for performing the actions described above. A system can be configured to perform specific operations or actions.
[0022] In general, one innovative aspect of the subject matter described herein is the synthesis of a ferroelectric material comprising Cu, Co, and Fe, and N. The act of melting one or more of d, Pr, Dy, or Tb to prepare a molten alloy, and spraying Using an atomizer, the molten alloy is fragmented with high velocity gas jets to separate the Cu, Co, Fe, and A droplet of a compound formed from one or more of Nd, Pr, Dy, or Tb is prepared. Other embodiments of this aspect can be embodied as a method comprising the steps of: Corresponding computer systems, apparatus configured to perform the actions of the above methods. and a computer program stored on one or more computer storage devices. Software that is installed on the system and that, when operated, causes the system to perform the actions described above. software, firmware, hardware, or a combination thereof. The above computer systems can be configured to perform specific operations or actions. and instructions which, when executed by a data processing device, cause said device to perform said actions. by causing one or more computer programs to perform certain operations or actions It can be configured as follows.
[0023] The above and other embodiments each optionally include one or more of the following features, either alone or in combination: Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb may be included in combination. Melting to produce the molten alloy includes melting Cu, Co, and Fe, as well as Nd, Pr, Dy, or The method may include induction melting one or more of Cu, Co, Tb to produce the molten alloy. and Fe, and one or more of Nd, Pr, Dy, or Tb are melted to prepare the molten alloy. The present invention relates to a method for manufacturing a ferroelectric material comprising the steps of: arc-melting Cu, Co, and Fe, and one or more of Nd, Pr, Dy, and Tb; cooling the molten alloy to produce the cast alloy. Producing a flake includes cooling the molten alloy to produce an ingot; remelting the cast alloy to form a second molten alloy; and cooling the second molten alloy to form the cast alloy. The method may include producing an alloy flake.
[0024] In some implementations, the method further comprises stirring the molten alloy with an argon purge. The Cu, the Co, the Fe, and the Nd, Pr, Dy, or Tb are contained in the entire molten alloy. The present invention includes uniformly distributing one or more of the following: Cu, Co, and Fe, as well as Nd, Pr, Dy, or Tb to prepare the molten alloy in an inert atmosphere. In the above, Cu, Co, Fe, and one or more of Nd, Pr, Dy, and Tb are melted in the melt. In the inert atmosphere, Cu, Co, and Fe are mixed to produce a fused alloy. The step of melting one or more of Nd, Pr, Dy, or Tb to prepare the molten alloy includes the steps of: In the inert atmosphere containing the base material, Cu, Co, and Fe, as well as Nd, Pr, Dy, or Tb, The method may include melting one or more of Cu, Co, and Fe, and Nd, Pr, Dy, or Tb. The step of melting one or more of the above to prepare the molten alloy is carried out at a pressure of 1.5 to 1.8 bar (150 to 180 bar). At a pressure of 100 kPa, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, and Tb are melted. and forming the molten alloy.
[0025] In some implementations, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb. The melting of the above to produce the molten alloy is carried out by vacuum induction to produce Cu, Co, and Fe, as well as and melting one or more of Nd, Pr, Dy, or Tb to prepare the molten alloy. Cu, Co, and Fe, and one or more of Nd, Pr, Dy, and Tb are melted, and the melt is The fusion alloy is made by melting Cu, Co, and Fe with Nd, Pr, Dy, or Tb at 1450°C. to form the molten alloy. melting one or more of Nd, Pr, Dy, or Tb in the alloy to prepare the molten alloy; In an alumina crucible, Cu, Co, and Fe, as well as one or more of Nd, Pr, Dy, and Tb, are melted. The molten alloy may include melting the alloy to form the molten alloy. or Tb to prepare the molten alloy. In a crucible, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb are melted, The molten alloy may include Cu, Co, and Fe, and Nd, Pr, Dy, or Tb. The step of melting one or more of Cu, Co, and CuN in a copper crucible to prepare the molten alloy is described below. and Fe, and one or more of Nd, Pr, Dy, and Tb are melted to prepare the molten alloy. This may include:
[0026] In some implementations, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb. Melting the above to produce the molten alloy comprises melting Cu, Co, and Fe in a high density crucible. and melting one or more of Nd, Pr, Dy, and Tb to prepare the molten alloy. It may include melting Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb, The step of preparing the molten alloy comprises preparing a molten alloy of Cu, Co, and Fe, as well as Nd, Pr, Dy, in a high purity crucible. or Tb to form the molten alloy.
[0027] In some implementations, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb. Melting the above to form the molten alloy includes melting Nd. Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb are melted to prepare the molten alloy. The step of melting may include melting Dy. The melting of one or more of Nd and Dy to prepare the molten alloy is The melting of Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb may include Melting Pr to form the molten alloy may include melting Cu, Co, and The molten alloy is prepared by melting Fe and one or more of Nd, Pr, Dy, and Tb. The melting of Cu, Co, and Fe, as well as Nd, Pr, Dy, or Tb, may be included. The step of melting one or more of these elements to prepare the molten alloy is to melt Pr and Tb. and
[0028] In some implementations, Cu, Co, and Fe, and one or more of Nd, Pr, Dy, or Tb. Melting the above to produce the molten alloy comprises melting Cu, Co, and Fe in a crucible, and melting one or more of Nd, Pr, Dy, or Tb to produce the molten alloy; And cooling the molten alloy to produce the cast alloy flakes includes cooling the molten alloy in the crucible. Cooling the molten alloy to produce the cast alloy flakes includes pouring the molten alloy onto a water-cooled wheel to produce the cast alloy flakes. Pouring the molten alloy onto the water-cooled wheel to produce the cast alloy flakes comprises: The method may include pouring the molten alloy onto a water-cooled copper wheel to produce a cast alloy flake.
[0029] In some implementations, cooling the molten alloy to produce the cast alloy flakes. is 10 5 and cooling the molten alloy at a rate of 100 Kelvin / second. The step of producing the cast alloy flakes comprises cooling the molten alloy at a rate of 10 to 100 Kelvin / second. Cooling the molten alloy to produce the cast alloy flake may include Fusion gold, 10 -1 This may involve cooling in a vacuum at a pressure above 10 bar (10 kPa).
[0030] In some implementations, a spray atomizer is used to spray the molten alloy with high velocity gas. The Cu, Co, Fe, and one or more of the Nd, Pr, Dy, or Tb are fragmented by injection. The forming of the droplets of the compound includes forming the molten alloy removing less than about 2 wt. % of the Cu, Co, Fe, and one or more of the Nd, Pr, Dy, or Tb from the The method includes fragmenting the molten alloy with high velocity gas jets using a spray atomizer. and forming the first layer from one or more of Cu, Co, Fe, and Nd, Pr, Dy, or Tb. The preparation of droplets of the compound may be carried out with an oxygen concentration of less than 0.04 wt%, or 0.12 at%, at most, or less than 0.00 %, a carbon concentration of less than 58 at.%, or both. In some embodiments, the droplets of the compound contain 0.00009 to 0.18 at % oxygen, or 0.028 to 0.1 at % oxygen. In some examples, the droplets of the compound may contain 0.0001 to 0.09 at% oxygen. % of carbon, or 0.0058 to 0.009 at % of carbon. The molten alloy is fragmented by high velocity gas jets to separate the Cu, Co, Fe, and the Nd, Pr, Dy, or The formation of droplets of the compound formed from one or more of Tb and Tb dissolves the molten alloy in water. The molten alloy may be fragmented with an inert gas jet using a spray atomizer. is fragmented by a high-velocity gas jet to separate the Cu, Co, Fe, and the Nd, Pr, Dy, or Tb. The step of forming droplets of the compound formed from one or more of the following is carried out by using a gas jet having a velocity of 500 m / s. and fragmenting the molten alloy by
[0031] In some implementations, a spray atomizer is used to spray the molten alloy with high velocity gas. The Cu, Co, Fe, and one or more of the Nd, Pr, Dy, or Tb are fragmented by injection. The droplets of the compound formed are formed by subjecting the molten alloy to a pressure of 0.18 to 0.58 MPa. The molten alloy is fragmented by gas jets using a spray atomizer. The Cu, Co, Fe, and one or more of Nd, Pr, Dy, or Tb are fragmented by a gas jet of The droplets of the compound formed from above may have an average diameter of 140 to 180 micrometers. Using a spray atomizer, the method may include producing droplets of the compound having a diameter of The molten alloy is fragmented by high velocity gas jets to separate the Cu, Co, Fe, and the Nd, Pr, Dy, or Tb, 3 of The method may include creating droplets of the compound having a density.
[0032] The subject matter described herein can be implemented in certain embodiments and includes the following: In some implementations, the process may provide one or more of the following advantages: In some implementations, grain boundary engineering (GBE) is used to Without compromising the magnetic performance and achieved values of the finished fully dense Nd-Fe-B sintered magnet. In some implementations, the GBE Nd-F eB magnet products offer improved performance, e.g. improved high temperature capability up to 200°C. In some implementations, the GBE may impose restrictions on the thickness of the magnet being processed. In some cases, there may be no limitations, e.g., the cost of sintered magnets compared to other forms of magnet processing. In some implementations, the GBE may be used to homogenously distribute additive materials throughout the entire surface of the substrate, e.g. For example, the amount of dopant material added to the magnetic powder can be controlled. GBE allows precise tuning of magnetic performance to meet application requirements. In the present study, the GBE is a final sintered magnet, e.g., NdFe 14 Maintain the original grain phase of B1, e.g., 2:14:1 phase However, additive materials can be precisely added to the sintered magnet to improve the performance of the sintered magnet. The final sintered magnet may contain no additive material in the grain phase or in the 2:14:1 phase. .
[0033] In some implementations, the final sintered magnets produced by GBE modification exhibit improved material corrosion properties. In some instances, the GBE modification process has the following advantages over other magnet processing techniques: The processing methodology, grain boundary property control, uniform mixing, composition and microstructure control, or any of these For example, the GBE modification process improves the microstructure of the initial sintered magnet. The microstructure can be manipulated to produce a final sintered magnet with improved magnetic performance. GBE System It is possible to control the microstructure, e.g., grain or domain size, of the final sintered magnet to improve corrosion resistance and magnetic properties. The GBE process can enhance the thermal performance of the grain matrix, e.g., NdFe 14 B Matric New grain boundaries in the grains, e.g., Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 Controlling the production of at% This can improve the corrosion stability of the Nd-Fe-B sintered or regenerated magnet body. In some implementations, GBE systems have demonstrated improved magnetic performance, resistance to intergranular degradation, and improved corrosion resistance. The final sintered magnets having the above properties are produced using the GBE system. The final sintered magnets are produced from recycled magnetic materials, virgin magnetic materials, or a combination of both. For example, the cast alloy flake and the rare earth-transition element additive material can be produced by It is possible.
[0034] The details of one or more implementations of the subject matter described herein are set forth in the accompanying drawings and the description below. Other features, aspects, and advantages of the subject matter will become apparent from the specification, the drawings, and the claims. Wax. [Brief description of the drawings]
[0035] BRIEF DESCRIPTION OF THE DRAWINGS [Figure 1] 1A and 1B show an example of a grain boundary engineering process.
[0036] [Diagram 2] FIG. 2 shows an example of a hydrogen mixing reactor.
[0037] [Figure 3A-E]3A-E show a reaction bottle that can be placed on a dolly that allows transportation of the reaction bottle in and out of the reaction chamber.
[0038] [Fig. 3F-G] 3F and G show an example of another hydrogen mixing reactor with a pair of reaction chambers.
[0039] [Figure 3H-J] 3H and 3J show a reaction bottle that can be placed on a dolly that allows transportation of the reaction bottle in and out of the reaction chamber.
[0040] [Figure 3K] FIG. 3K shows an example of a storage container.
[0041] [Figure 4] FIG. 4 is a graph showing examples of the range of properties of starting materials.
[0042] [Diagram 5] FIG. 5 compares the composition of the original material (shown in the left column) with the finished magnet product (shown in the right column).
[0043] [Figure 6-8] 6-8 are graphs showing example properties of magnets processed using grain boundary engineering.
[0044] [Figure 9] FIG. 9 is an example of a process for applying grain boundary engineering techniques.
[0045] [Figure 10] FIG. 10 shows an example of a spray atomizer.
[0046] [Figure 11] FIG. 11 shows a graph comparing the corrosion resistance of the GBE final magnet with other Nd—Fe—B magnets.
[0047] [Figure 12] 12A and B show the reversible decrease α in remanence of the starting and final magnets.
[0048] [Figure 13] 13A and B show the reversible decrease β in coercivity of the starting and final magnets.
[0049] [Figure 14] FIG. 14 shows a graph of exemplary properties of the final magnet.
[0050] [Figure 15] FIG. 15 shows some examples of the magnetic performance of discarded sintered magnets and recycled magnets.
[0051] [Figure 16] FIG. 16 shows an example of the demagnetization curve of an unprocessed magnet using the GBE process.
[0052] [Figure 17] FIG. 17 shows an example of a demagnetization curve for a magnet fabricated using the GBE process.
[0053] [Figure 18] FIG. 18 is a block diagram of a computing system that may be used in connection with the computer-implemented methods described herein.
[0054] Like reference numbers and designations in the various drawings indicate like elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] (Detailed Description) The process can be used to determine, for example, particle size, alignment, density, energy product (BHmax), remanence, Nd2Fe with specific performance characteristics, such as a desired combination of magnetic field strength (Br) and coercivity (iHc). 14 B For example, the grain boundary engineering (GBE) process can be used to fabricate grain boundary modified lithium carbide. The GBE process can include the production of new magnetic materials, including Nd-Fe-B permanent magnets with different phases. Recycled magnetic materials, e.g. from those never before used in consumer products , e.g., new magnets from those previously used in consumer products, or both. The GBE process may also be referred to as a grain boundary modification (GBM) process.
[0056] As described in more detail below, the GBE process modifies the grain boundary phase of the starting magnetic material. While maintaining the original grain phase of the starting magnetic material. For example, the new Nd2Fe 14 B. Create a magnet In this case, the GBE system is able to reduce the amount of Nd-Fe-B 2:14:1 phase grains from the starting materials in the final magnetic product. The GBE system retains all or substantially all of the Nd-rich grains. The grain boundary phase may be replaced with new grain boundary phase made from the additive material. The GBE system may have about 90 to about 99.9 vol% of the starting materials in the final magnetic product, e.g., 2:14:1 Preferably, about 92 to about 99.75 vol.% of the starting materials are in the final magnetic product. For example, 0.25 to 8 at % of the final magnetic product is additive material. In some instances, the GBE system maintains about 90 to about 97 vol.% of the starting material. The GBE system replaces about 3 to about 12 vol% of the Nd-rich grain boundary phase with a new grain boundary phase. For example, the GBE system requires 300 Ω for magnets with Br of 1.48 to 1.55 T and iHc of 800 to 1000 kA / m. The Nd-rich grain boundary phase can be replaced by 4.8 vol% of Nd, and the Br is 1.31 to 1.38 T and the iHc For magnets with a current density of 1300-1700 kA / m, 6 to 7.2 vol% of Nd-rich grain boundary phase should be replaced. or 9 to 12 vol% for magnets with Br of 1.18 to 1.26 T and iHc of 1800 to 2500 kA / m. can replace the Nd-rich grain boundary phase in (all values included).
[0057] In some implementations, the GBE system is adapted to heat the alloy and Pure elements may be melted, for example, Nd-Pr, Fe-B, and Fe. Some exemplary alloys are: , the following elements: (i) Nd, Pr, Fe, FeB, and B; (ii) Nd, Fe, Co, Cu, and Dy; or (iii) ) Nd, Fe, Co, Cu, Dy, a composition with a ratio of Nd75:Pr25, a composition with a ratio of Dy80:Fe20, and Pr In some instances, one or more of these elements may be combined with an alloy of other elements. You can also match them.
[0058] The GBE system transfers the molten alloy onto a water-cooled copper wheel that rotates at approximately 35 revolutions per minute (RPM). to form a cast alloy flake. The cast alloy flake may have a thickness of about 0.2 mm. The cast alloy flakes may have a grain size ranging from about 5 μm to about 80 μm. In some instances, waste magnet material, e.g., waste magnetic material left over from the construction of other magnets, is used to , the cast alloy flakes may be formed.
[0059] The GBE system uses, for example, a jet mill process to pulverize the cast alloy flakes to a size of about 0.9 mm. The GBE system produces fine powders of particles with sizes ranging from about 15 μm to about 20 μm. The fine powder was pressed in a magnetic field ranging from 400 kA / m to 1200 kA / m at about 5°C to about 15°C under a rectangular shape. The GBE system applies pressure to fine powders directly perpendicular to the magnetic field. The rectangular molded body may have a length of about 35 mm, a width of about 37 mm, and a height of about 40 mm.
[0060] The GBE system sinters a rectangular compact at about 1070°C to produce a sintered compact, e.g., Nd-Fe The sintered compact or other sintered Nd-Fe-B magnet compacts are then processed into a sintered Nd-Fe-B block. , processed by the GBE system using grain boundary engineering process, the Nd-Fe-B sintered block, e.g. For example, only the rare earth rich phase of an Nd-Fe-B magnet is modified. , to modify the Nd-rich grain boundary phase of the Nd-Fe-B sintered block.
[0061] For example, the GBE system transfers Nd-Fe-B sintered blocks to a mixing reactor and adds additives. The material, for example, Nd-Pr, or Nd-Dy-Co-Cu-Fe, or Nd-Dy, is put into the mixing reactor.
[0062] GBE systems can be run in either an inert atmosphere or a hydrogen atmosphere, to name a few. In the present invention, the powder produced from the sintered block may be mixed with additive materials. When mixing at 5 RPM, the GBE system mixes the powder and the additive material at least 1 The mixture may be mixed for 5 hours. In some examples, the GBE system may be A thermal cracking process, for example a hydrogen thermal cracking process, is used to produce fine powder. The system is Nd2Fe 14 Separating the 2:14:1 phase grains 20 from the Nd-rich grain boundary phase 30 in the B magnet 10, or Similarly, any suitable method may be used to separate the grains of the phase from the grain boundary phases of other types of magnetic materials. possible.
[0063] In some instances, the mixing may include both coarse and fine mixing. For example, By coarse mixing, particles with an average size of 1 μm to 2000 mm can be produced from the sintered block. The mixing step consisted of evacuating the mixing reactor and then introducing hydrogen at a pressure of 0.9 bar (90 kPa). and
[0064] After mixing, the GBE system transfers the combined powder formed from the sintered block and additive materials to the chamber. The combined powder is exposed to hydrogen at high temperature to absorb hydrogen. The GBE system is then The combined powders were mixed in situ at 600° C. until a vacuum was restored in the reactor. Partially degassing. For example, during processing, the GBE system oxidizes the Nd-rich grain boundary phase. The GBE system may be configured to have a Nd-rich grain boundary phase, so that the grain boundary phase does not react with hydrogen. The material may be sieved to remove the Nd-rich grain boundary phase material from the Nd-Fe-B grains.
[0065] The GBE system then further homogenizes the combined powders using a jet mill process. , achieving an approximate fine powder particle size of 0.9-3.5 μm. The GBE system then The combined powder may be sieved to remove large oxidized particles. The sieving may be a separate sieving process to remove the thick intergranular phase material. Good too.
[0066] The GBE system compresses fine combination powders in an inert atmosphere at 5-15°C in a magnetic field. The powder may be compacted to form a magnetized green compact. GBE Systems Alternatively, the powder compact may be transferred to a hydraulic chamber and subjected to an isostatic pressure of 60 MPa. For example, the GBE system is capable of determining the final density of a sintered product, e.g., after sintering and annealing. , so as to be close to the theoretical value, for example, 4.5 g / cm 3 The powder compact is then pumped into a hydraulic chamber so that In some instances, the GBE system may be pressed in a magnetic field, for example. The density of the magnetized green compact is 4.5g / cm 3 If the pressure exceeds 100 kPa, the powder compact is placed in a hydraulic chamber. The finely divided combined powders may be compacted in the magnetic field without being pressed in a magnetic field.
[0067] The GBE system sinters and anneals the green compacts under vacuum, for example in a sintering chamber. Once the sintering temperature is reached, the Ar partial pressure in the sintering chamber is adjusted to 200 to 500 millisieverts absolute. For example, the pressure can be adjusted to 20 bar (20 to 50 kPa) at the maximum sintering temperature. The introduction of Ar after about 10 minutes of sintering is effective in preventing the sintering process from reaching a sufficient density, e.g. This can help achieve a sufficiently dense sintered magnet.
[0068] In some implementations, the result of GBE processing is a modified cellulose membrane, as shown, for example, in FIG. 1. A fully dense Nd-Fe-B sintered magnet 40 having a clear grain boundary 50, in which the GBE system , the amount of doped or additive material in a fully dense sintered magnet can be controlled. The E process is a reproducible and precise method for tailoring the magnetic performance of sintered magnets. The heavy rare earth elements, such as Dy and Tb, can be significantly reduced, and a sufficiently high density sintered magnet can be obtained. Uniform distribution of additive material throughout, e.g., throughout the modified grain boundaries 50, and For example, customized microstructure designs according to customer requirements may be provided.
[0069] The new Nd-Fe-B product 40 offers improved temperature resistance (coercivity, iHc), temperature profile, and The GBE process can reduce the input requirements of dysprosium (Dy) materials. The GBE process produces 81-99.9 at% magnetic material. The GBE process may be combined with a rare earth element additive of 0.1 to 19 at %. The process may have high affinity for collection and improved magnetic performance. Could this reduce end-user vulnerability to rare earth supply risks and rare earth price fluctuations? could play an important role in creating a sustainable magnet supply chain, In some implementations, the composition of the material input requirement Costs are reduced by utilizing less Dy material input. Together, resource requirements in terms of materials, waste, pollution, and energy can be reduced.
[0070] The method for GBE may employ methods for oxygen inhibition, for example using grain boundary engineering. The Nd-Fe-B sintered magnets manufactured using this method have a content of 1.98 at% or less, or 1.32 at% to 1.98 at% (both ends) The Nd-Fe-B sintered alloys may have an oxygen content of 0.1 to 1.0 μm, including the oxygen content of 0.1 to 1.0 μm. Some examples of atomic percentages of oxygen content in magnets are 1.00 at%, 1.10 at%, 1.32 at%, at%, 1.33at%, 1.49at%, 1.51at%, 1.74at%, 1.81at%, 1.83at%, 1.91at%, and 1.98 at% is an example.
[0071] The method may include the addition of new rare earth material in the range of 0.1 to 19 at % of the starting material. Some further implementation details and optional features include the specific Nd-Fe-B magnet that is desired. Such performance characteristics include operations that maintain, enhance, and / or provide stone performance characteristics. These include particle size, alignment, density, energy product (BHmax), remanence (Br), and Any desired combination of coercive forces (iHc) may be included.
[0072] In the mixing stage, the ingredients are mixed and mixed to achieve the desired final properties in the finished product. The mixing process may involve crushing, grinding, milling, or otherwise reducing the material to a coarse powder. The use of hydrogen to cause the decay may be included. In some implementations, a magnet, e.g., Nd -Fe-B or Sm2Co 17 The magnets are processed into powder using a hydrogen mixing reactor, and the powder is The material is combined in situ with additives to improve coercivity.
[0073] The processes for mixing include milling, cutting, and high energy ball milling. , roller milling, sawing, jet milling, rolling, shaking, jaw crushing In some implementations, hydrogen mixing is used to mix the starting material and the new This is a process for homogenizing rare earth element additives. The element is the φ phase of the magnet, e.g., Nd2Fe 14 B and rare earth rich grain boundaries, and the rare earth element Hydrogen absorption and hydrogen react with hydrogen trapped in the crystalline structure to form hydrides. As a result of the formation of oxides, the crystal structure expands and breaks the brittle structure. It may be effective in fragmenting the ingredients and additives as well as in crushing the ingredients.
[0074] As used herein, the term "fragmentation" refers to the mechanical, chemical, thermal, or radiation-induced fragmentation of solid materials. This includes any type of resolution, including any suitable process, including mechanical resolution, mechanical resolution, or a combination of these. The degree of fragmentation can range from coarse division to complete disintegration into a fine powder.
[0075] Hydrogen mixing reaction with the addition of required rare earth element additives and / or hydrides of unused elements In situ production of the desired fine and impurity-free powder mixture using a Nd-Fe-B sintering furnace It may be effective in improving the magnetic properties of the magnetic materials. To improve physical properties, such as density or corrosion resistance, 0.1 wt% to 19 wt%, preferably The magnetic material may contain 1% of additive elemental additives. This additive and the magnetic material are mixed with hydrogen and then cooled. The reactor is charged with Pr in which x is in the range of 1 to 3 mole fraction. 75 Nd 25 H x Rare earth coarse powder mix containing It may also generate things.
[0076] FIG. 2 shows a hydrogen mixing process in which a magnetic material, such as a sintered magnet, is broken down into particles and the particles are mixed. An example of a reactor is shown. The magnetic materials include waste magnetic materials, magnetic materials from end-of-life products, or newly created magnetic materials, e.g., that have never been used in a consumer product. In some examples, the magnetic material is made from recycled magnetic material. The magnet may be derived from a newly formed sintered magnet.
[0077] In some implementations, a hydrogen mixing reactor mixes elemental additives with the particles. In the primary mixer reactor, the target average diameter is about 1 micron to about 2 millimeters, or about 4 to about 7 microns. Hydrogen mixing reactors are disposed in each of the mixing chambers 122, 124. The mixing chambers 122, 124 each have a lining 110. The lining 110 contains a magnetic material and allows magnetic flux to pass around the magnetic material through an opening in the lining 110 . This facilitates the flow of gas through the
[0078] When one of the vessels 102, 104 is filled with hydrogen gas while the vessel contains the rare earth material, Hydrogen mixing causes fragmentation of the magnetic material. Exposure to hydrogen gas lasts for approximately 1-40 hours. The exposure may last for a period of time. The exposure may be for a shorter or longer period of time, and the pressure and temperature The process engineering requirements and other processing steps used to achieve the target particle size are taken into consideration. stage, other processing stages used to achieve the desired homogeneous mixture, or The selection may be based on any combination of two or more of these.
[0079] To ensure that hydrogen mixing does not cause the collapse of the magnets within the reaction vessels 102, 104 and ensure that particulate matter accumulation does not interfere with exposure of some magnetic materials to hydrogen gas. To achieve this, a diffusion promotion device 112 with an opening such as a snorkel or pipe is used. Agitators, blowers, or gas supplies or other flow enhancers (not shown) may be installed in the container. This can help promote hydrogen gas flow within the vessels 102, 104. The magnetic material that falls from the openings in the lining 110 The material may be agitated by an agitator located at the bottom of each vessel 102,104.
[0080] For introducing magnetic material into the containers 102,104, a removable lid 114 may be provided. For example, the magnetic material may be disposed in the containers 102, 104 shown in FIG. With or without a controlled environment, the material is transferred to the interior of the lining 110 by conveyor or by hand. The properties of the final product made from the magnet can be determined by pre-determined specifications of residual magnetism, A small number of rare earth transition element additive materials are used to improve the energy product and / or coercivity. In some instances, after mixing, crushed magnetic material may be added to the lining 110. Additives may be added to the ingredients to adjust the properties of the final product. Some examples of additive materials are: The elements are Nd, Pr, Dy, Gd, Tb, La, Ce, Yb, Ho, or Eu, or two or more of these. Combinations of the above are possible.
[0081] The vessels 102, 104 can withstand a predetermined pressure. For example, a hydrogen mixing reactor can be A vacuum pump may be included. In some implementations, the pressure is up to 60 bar (6 MPa). Similarly, the containers 102, 104 can withstand lower pressures. , a thermostatically controlled heater 116 and a pressure regulator control.
[0082] The hydrogen mixing reactor is connected to vessel 102 via pump assembly 128 and valve assembly 133. 104 includes a gas supply connection 138 for introducing hydrogen or other gas into the pump assembly. The valve assembly 133, the gas management element 144, or a combination of two or more of these, , by feeding gas directly into the diffusion facilitating device 112 to the entire volume of the magnetic material in the containers 102, 104. In some examples, the pump assembly 128 and The valve assembly 133 connects the vessels 102, 104 to allow, for example, degassing or initial gas Filling, e.g. pumping gas from one vessel to another to recycle hydrogen gas Transfer by, for example, discharge to atmosphere using ambient connection 132 to the outside atmosphere, container 102, pressurizing 104, backfilling one or both of the vessels 102, 104 with an inert gas, etc. or a combination of two or more of these; The controller 140 may be configured to control the valve assembly 133 and and pump assembly 128 to facilitate the hydrogen mixing process and the hydrogen supply between vessels 102, 104. The transfer may be automated.
[0083] During the hydrogen mixing process, the magnetic particles are passed from the vessels 102, 104 through the chute 126 and into the The magnetic particles fall into chamber 120. The magnetic particles are removed from chamber 120 for further processing. In some implementations, the opening between the chute 126 and the vessels 102, 104 may include A pressure-resistant valve may be employed.
[0084] In some implementations, one of the vessels 102, 104 is made airtight and includes a gas management element 144. The selected vessel 102, 104 is then evacuated using, for example, a pump assembly. 128, hydrogen from a gas supply is filled, and the selected vessel 102, 104 is then magnetically The materials may be prepared for mixing and fragmentation. After mixing and fragmentation, e.g. venting hydrogen from the selected vessel 102, 104 and transferring the hydrogen to the other vessel 104, 102; The hydrogen may then be transferred to the other vessel 104, 102 by the gas management element 144. As the contents of each vessel are subjected to hydrogen mixing, hydrogen is collected and fed to the other vessel 102, 1 04 and the hydrogen mixing process can be repeated in the other vessel. can be done.
[0085] In some implementations, a gas storage chamber is included within the gas management element 144, and the container 1 Hydrogen vented from one of the vessels 102, 104 may be refrigerated before being transferred to the other vessel 102, 104, e.g. During the mixing cycle, the gas is temporarily stored in the gas storage chamber (not shown). The use of a storage chamber may allow the hydrogen mixing reactor to include only one vessel. In some instances, the hydrogen mixing reactor may include three or more vessels. The members minimize pressure drop or pressure rise during transfer, thereby reducing the pressure in the chamber and the volume. The energy consumption of the gases is selected to maximize the energy economy associated with transporting the gases to and from the vessels 102, 104. The stage may include a plurality of chambers each having a different volume.
[0086] FIG. 3A shows a set of four reaction bottles 212 on a cart 216. The cart 216 holds the reaction bottles 212. 12 into and out of one of the reaction chambers, for example, reaction chambers 202, 202′ shown in FIG. 3F. The reaction chamber 202, 202' may be used in conjunction with or in place of the hydrogen mixing reactor shown in FIG. In some examples, the reaction bottle 212 may be a hydrogen mixing reaction bottle as shown in FIG. For example, the gas management element 144 may be used with a reactor, such as the vessels 102, 104. Bottle 212 can be filled with an inert gas, such as Ar or N, followed by The magnet is filled with magnetic material, e.g., a freshly sintered magnet. A magnetic material 206 , such as a magnet, may be loaded into a transfer chute 208 into a reaction bottle 212 . To prevent contamination of the magnetic material 206, e.g., by oxygen, the magnetic material 206 is inert. At ambient temperature, reaction bottle 212 may be filled.
[0087] In some implementations, a small portion of the rare earth transition element additive material is added to the reaction bottle 212. The rare earth transition element additive material may be a magnetic material 206 and a rare earth transition element additive material. The properties of the final product produced from the and coercivity. In some examples, the reaction chambers 202, 202 After mixing and fragmentation of the materials in the ', the hydride of the rare earth transition element additive material is hydrogenated. It may be added to the magnetic material 206 .
[0088] Each reaction bottle 212 is fitted with a snorkel 213 or other device that facilitates gas diffusion within the reaction bottle. For example, the snorkel 213 may have openings on the sides that allow for the diffusion of gas. The bottles 212 may be cylindrical with a nozzle so that the gas can pass through the nozzles located in the center of each bottle 212. It reaches the magnetic material.
[0089] The bottle 212 and the snorkel 213 are open at the top, and hydrogen gas enters the bottle 212 and the snorkel. 213 and come into contact with the magnetic material 206 contained within the bottle 212. 2 and / or may allow the magnetic material 206 to be filled into the bottle 212.
[0090] When a magnetic material 215, e.g., a magnet, is located within the bottle 212 shown in FIG. A cover 214 is attached to the cart 216 to isolate the bottle 212 and its contents from the outside atmosphere. The container formed by the cover 214 and the dolly 216 may have an internal volume filled with an inert gas. The gas atmosphere is maintained and ambient air is prevented from coming into contact with the magnetic material 215. For example, in the inert atmosphere, the magnetic material 215 is After the tank 212 is filled, the bottle 212 may be covered with a cover 214 and the cart 216 may be For example, FIG. 3E shows a filled bottle 212. on the dolly 216 and before placing the cover 214 on top of the filled bottle 212. 2 shows an example of a filled bottle 212. The bottle 212 is filled while placed on a cart 216. or may be filled and then placed on the cart 216.
[0091] 3F-G show an example of another hydrogen mixing reactor with a pair of reaction chambers 202, 202′. The reaction chambers 202, 202' are connected to the gas management element 144 as described above. Interconnected by element 144. Gas source 138 supplies a number of gases, e.g., an inert gas. and hydrogen may be provided. Peripheral connection 132 may be vented to atmosphere. The gas management element 144 may provide a hole between the gas containers 102, 104 instead of between the gas containers 102, 104. in terms of transferring gas from one reaction chamber 202 to the other 202' and vice versa. It operates as described above with reference to FIG.
[0092] A covered carriage 260, such as carriage 216, is disposed in the first of the reaction chambers 202. Meanwhile, in the other reaction chamber 202′, e.g. Hydrogenation is being performed on bottles placed on a separate cart within chamber 202'. Once the covered cart 260 enters the reaction chamber 202, the cover 214 is removed from the cart 260. The door 252 on the reaction chamber 202 is then closed. The reaction chamber 202 is then For example, the reaction chamber 202 may be transferred from another reaction chamber 202' after processing in the other reaction chamber 202' is completed. The chamber may be filled with an inert gas.
[0093] The gas management element 144 supplies hydrogen from a hydrogen source to the reaction chamber 202 to react with the required For example, when hydrogenation in reaction chamber 202' is completed, the pressure may be achieved by The gas management element 144 transports hydrogen from the reaction chamber 202' to the reaction chamber 202; The reaction chamber 202 is pressurized to a target pressure. The gas management element 144 Hydrogen gas, e.g., hydrogen gas, may be introduced from the bottle 212 into the interior of the bottle 212 through the cover 232 or other opening in the bottle. Hydrogenation may be initiated within reaction chamber 202 by introducing pressurized hydrogen gas. stomach.
[0094] The hydrogen mixing process may be, for example, when a hydrogen mixing reactor performs the initial mixing process. For example, a hydrogen mixing reactor may be used to perform the second mixing process. In practice, magnetic particles having average diameters of about 4 microns to about 7 microns can be produced. In some instances, both processes may be carried out in the hydrogen mixing reactor shown in Figures 3F-3G. Preferably, both processes may be carried out in the hydrogen mixing reactor shown in FIG. One process may be carried out in one of the reactors, and the other process may be carried out in the other reactor. For example, the first mixing process may be carried out in a hydrogen mixing reactor as shown in FIG. and the second mixing process may be carried out in a hydrogen mixing reactor as shown in Figures 3F-3G.
[0095] The gas management element 144 may be configured to evacuate gas from the reaction chamber 202′, for example, completely, to reduce the amount of gas in the reaction chamber. The gas may be admitted to the reaction chamber 202 for use during processing within the chamber 202, Alternatively, the reaction chamber 202 may be placed in a storage chamber or container. The heater 257, which is controlled by a thermostat, is adjusted by a controller to reach the target temperature. Degrees may be provided.
[0096] As the hydrogenation process proceeds within the reaction chamber 202, the gas management element 144 The reaction chamber 202' is then backfilled with an inert gas. Then, as shown in FIG. 3G, The doorway 252' to the reaction chamber 202' is opened and the cover 214' is placed on the dolly 260'. The hydride magnet material, now reduced to particles, is then reacted in carriage 260'. It moves outside the chamber 202'.
[0097] After hydrogenation in the reaction chamber 202 is completed, the gas management element 144 removes excess hydrogen gas. The hydrogenation process is then carried out in the reaction chamber 202. 02′, and begins again with one or more bottles 212 disposed within the The excess hydrogen gas is pumped from reaction chamber 202 to reaction chamber 203 while leaving some hydrogen material in the reaction chamber. It may be transferred to bar 202'.
[0098] In some implementations, the bottle 212 uses a cover 232 as shown in Figures 3C, 3D, and 3J. The cover 232 acts as a funnel and can be closed when the valve 234 is open. For example, when the bottle 212 is in an upside down position, the recovered hydride magnet particles The cover 232 can be removed to allow the , allowing the magnetic material 206 to enter the bottles 212 and then placing a cover 232 over each bottle 212. You may do so.
[0099] Referring to FIG. 3J, in an inert atmosphere, a cover 232 is placed over the bottle 212 and the The bottle can be sealed and removed from the inert atmosphere without the need for a cover 214. The bottles 212 may be transported by a dolly 216 or individually.
[0100] 3K shows an example of a storage container 240 for magnetic particles received from the bottle 212. A valve 234 on 212 receives a nozzle 265 on the storage vessel 240 and a manifold 267 for bottoming. The air is sealed into a snorkel 213 within the manifold 212. A blower 266 is connected to the snorkel 213 via a manifold 267. Inert gas is supplied into the tank 213, and the magnetic particles are taken from the bottle 212 into the storage container 240. After entering one of the bottles 212, the inert gas flows back into the storage chamber 240. You may do so.
[0101] The inert gas is introduced into the bottle 212 and the snorkel 213 as shown in FIG. 3H, which is a cross-section of the bottle 212 and the snorkel 213. The flow may exit the snorkel 213 in a linear or radial flow (or both). The tangential pattern of inert gas discharged through a tangentially oriented slot in a kerosene filter 213. The tangential pattern of the inert gas flow dislodges particles from the interior walls of the bottle 212. , may help facilitate complete removal of the magnetic particles from the bottle 212.
[0102] The valve 234 may be, for example, a gate structure that allows the nozzle 265 to enter the interior of the bottle 212. When the bottle 212 is removed, a cover 268 is placed on the nozzle 265. , the reservoir 240 may be sealed.
[0103] FIG. 4 shows the starting materials, e.g., recycled magnets from various different types of consumer products. 1 is a graph showing an example of a range of properties for a variety of different magnetic properties. The depicted bubble-like shape 302 represents the approximate range of starting materials to which the present process can be applied. The process may also be applied to other starting materials outside of shapes 302 such as bubbles.
[0104] Figure 5 shows the composition of the original magnetic material shown in the left column and the composition produced by this process shown in the right column. The composition of the rare earth metals in the starting material is shown in Fig. 1. It may be greater than or less than 18 at %, which is represented by the "R" area of the column. The rare earth metal may be contained within the grains of the original magnetic material or may be contained within the grain boundary phase material. During processing, a certain amount of rare earth metal "X" may be removed from the starting magnet material, e.g., as grain boundary phases. For example, the GBE system removes virtually all of the Nd-based The final Nd-Fe-B product has a composition similar to that of the original magnet. To achieve this, new rare earth materials, i.e., new materials, must be added. The rare earth material, e.g., the additive material, replaces the Nd-rich grain boundary phase that was removed from the original magnetic material. Can be replaced.
[0105] In FIG. 5, the initial material is represented by the "V" area, which is the rare earth material removed during processing. The final percentage of rare earth metals in the finished product is approximately equal to the amount of rare earth metal, i.e. "X". At least a percentage in the starting magnetic material, but not more than 18 at %. The percentage of rare earth material in the material, "R", is approximately equal to the lower of the two dashed lines in the left column. If the concentration is low, for example, less than 18 at%, the finished magnet products shown in the right column The final rare earth atomic percentage in the SiO2 solution is at least 100%, as depicted by the lower dashed line carried over. However, if the percentage of rare earth metal in the starting material is 18 If the atomic percentage exceeds 18% in the right column, the atomic percentage in the finished magnet will be 18% or more. The upper limit is indicated by the dashed line, which limits the amount to 18%.
[0106] In the finished product, the final rare earth atomic percentage is the initial rare earth atomic percentage of each component Nd, Pr, Dy, Gd , Tb, La, Ce, Yb, Ho, and / or Eu are 0.1 to 19% of their percentages in the original material. at %, and the atomic percentage of Nd or Pr or both is greater than zero Some implementations are further explained by the following formula: R=s(Nd )+s(Pr)+s(Dy); in the final Nd-Fe-B product as defined in paragraph 19, T=f (Nd) + f(Pr) + f(Dy); and added initial material V = Nd[p] + Pr[q] + Dy[r] (formula For the final product, 0.1≦p+q+r≦19at% and T≧min(R,18at%). To illustrate, consider the following example: If the atomic percentage values of Nd, Pr, and Dy in the starting magnet material are: If the values are 9.77, 2.96, and 0.92, respectively, the corresponding values can be calculated using the formula R = s(Nd) + s(Pr) + s(Dy ), we get R = 9.77 + 2.96 + 0.92, or R = 13.65. The atomic percentages of Nd, Pr, and Dy in the new Nd-Fe-B sintered magnets were 10.74, 3. 26 and 0.91. The value of the new Nd-Fe-B sintered magnet is calculated by the formula T = s(Nd) + s(Pr) + s(Dy ), T = 10.74 + 3.26 + 0.91, or T = 14.91. Materials were added during the GBE process, and the initial materials were 0.01% Nd, 0.01% Pr, and 0.01% Dy. For atomic percentage values of 0.2, 0.3, and 0.4, the equation V=Nd[p]+Pr[q]+Dy[r] is: V = 0.2 + 0.3 + 0.4, or V = 0.9. The formula for the initial material, i.e., V, is subject to two constraints: The final product satisfies 0.1≦p+q+r≦19 at% and T≧min(R, 18 at%). In the example, p+q+r=0.9 at% which is the first constraint, i.e., the p+q+r value is less than 0.1 at% This example also satisfies the requirement that the content of the first-use material must be 19 at % or more. The second constraint on the formula is: T is greater than or equal to the smallest value of R or the set of 18. In this example, Therefore, T is 14.91, and the minimum value of R or the set of 18 is R, which is 13.65, so T is , R or greater than the minimum of the set of 18.
[0107] In some implementations, V=Nd[p]+Pr[q]+Dy[r] (where 0.1 for the final product) ≦p+q+r≦15at%, and T≧min(R,18at%). In some implementations, V=N d[p] + Pr[q] + Dy[r] (wherein, for the final product, 0.1≦p+q+r≦12at% and T≧min( In some implementations, V=Nd[p]+Pr[q]+Dy[r], where , 0.1≦p+q+r≦8at% and T≧min(R,18at%) for the final product. In practice, V = Nd[p] + Pr[q] + Dy[r] (where 0.1 ≦ p + q + r ≦ 5a for the final product). t%, and T≧min(R,18at%). In some implementations, V=Nd[p]+Pr[q ]+Dy[r] (wherein, 0.1≦p+q+r≦3at% and T≧min(R,18at%) for the final product) In some implementations, V = Nd[p] + Pr[q] + Dy[r], where 0.1≦p+q+r≦2 at% and T≧min(R,18 at%). V = Nd[p] + Pr[q] + Dy[r] (wherein, 0.1≦p+q+r≦1at% for the final product, and T≧mi n(R, 18 at%).
[0108] In some implementations, X is the at% RE (Nd, Pr, Dy) removed from the original magnet. , and p+q+r≧X. In some implementations, the additives are where f is the atomic percent fraction of the starting Nd-Fe-B sintered magnetic material, f(Nd)+f(Pr)> 0. In some implementations, f(Nd)+f(Pr)+f(Dy)≦18. In some implementations, f(Co)≦3. In some implementations, f(Cu) ≦0.3. In some implementations, f(Fe)+f(Co)≦77. In this case, f(Dy)+f(Nd)+f(Pr)≧R.
[0109] In some implementations, the elemental addition is Nd[0.1-19 at%×s(Nd),x]Pr[0.1-19 at %×s(Pr),y]Dy[0.1~19at%×s(Dy),z]Co[0,d]Cu[0,e]Fe[0,f] (where [m, n] denotes the range between the minimum value m and the maximum value n; s(t) denotes the starting composition. f(t) is the percentage of atoms of element t in the final composition; x=18-[81,99.9]at%×(s(Nd)+s(Pr)+s(Dy)); y=18-[81,99 .9]at%×(s(Nd)+s(Pr)+s(Dy));z=18-[81,99.9]at%×(s(Nd)+s(P r)+s(Dy));d=3-[81,99.9]at%×s(Co);e=0.3-[81,99.9]at%×s(Cu) ;f = 77-[81,99.9]at% × (s(Fe) + s(Co)).
[0110] In some implementations, (i) a virgin material, e.g., Nd p Pr q Dy r is 0.05% for the final product. It is necessary that p+q+r is within the range of 1≦p+q+r≦19 at %, and T≧min(R,18) (wherein T= f(Nd)+f(Pr)+f(Dy), and R=s(Nd)+s(Pr)+s(Dy);(ii) p+q+ r≧X, where X is the at% RE(Nd, Pr, Dy) removed from the original magnet; ) T≦18 at%; (iv) f(Nd)+f(Pr)>0, where f is the atomic percent fraction of the final product. (v) f(Nd)+f(Pr)+f(Dy)≦18; (vi) f(Co)≦3; (vii) f(Cu)≦0.3; (viii) f(Fe)+f(Co)≦77; and (ix) f(Dy)+f(Nd). +f(Pr)≧R.
[0111] Besides the rare earth metals, the balance of both the starting magnetic material and the finished magnet is Fe, Co, Cu, Al, and other elements. In some instances, other types of magnetic materials may be used. Final magnet products made using other types of magnetic materials may have different magnetic material compositions. do.
[0112] The following example illustrates how a starting magnet material is processed according to grain boundary engineering techniques to reduce cost and supply vulnerability. More efficient use of dysprosium (Dy) in Nd-Fe-B final products that can reduce and its content are optimized while maintaining or improving certain magnetic properties, including remanence (Br). with minimal loss of magnetic performance; and includes temperature resistance (iHc) and temperature profile It is demonstrated that it is possible to produce a final Nd-Fe-B magnet with other property improvements. In practice, the method is not limited by the thickness of the magnetic material. For example, Nd-Fe-B final Additives of rare earth and transition elements to the grain boundary phase of the product, e.g. Nd 1-20 Dy 1-60 Co 1-60 Cu 0.1-20 Fe 0.5-90 at%, Nd 7-14 Dy 30-50 Co 28-45 Cu 1-10 Fe 1-10 at%, Nd 8.5-12.5 Dy 35-45Co 32-41 Cu 3-6. 5Fe 1.5-5 at%, or Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The use of at% is Nd-Fe-B final product Allows products to be of any thickness, e.g., greater than 6 mm It is possible. EXAMPLES
[0113] Example 1 These embodiments use a GBE process to produce permanent magnets with minimal amounts of dopants. This demonstrates that the GBE process can improve the overall magnetic performance of a stone. For example, the GBE process is shown in Figure 6. 27% increase in coercivity and 0% decrease in remanence as shown in FIG. 83% increase in force and 6% decrease in remanence, or 60% increase in coercivity as shown in FIG. and a 3% decrease in remanence. For example, FIG. 6 shows the effect of adding 0.5 at. For example, the following is an example of a modification of Nd-Fe-B type sintered magnet with Nd or Dy that results in high energy: The final magnet with 0.5 at% addition had a remanence (Br) of 1.423 T and a coercivity (iHc) of 1042 kA / m. , and 391 kJ / m 3 FIG. 7 shows the energy product (BHmax) of 3 at. % addition, e.g. This is a variation of Nd-Fe-B type sintered magnets with Dy that provides high coercivity suitable for high temperature applications. As an example, the final magnet with 3 at% addition had a remanence (Br) of 1.29 T and a coercivity ( iHc), and 323 kJ / m 3 The energy product (BHmax) of both magnets is 7.56 g / cm 3 in be.
[0114] In one example, a magnet having the properties shown in FIG. 6 may include 0.5 at % Nd dopant. The starting material for the magnet was the "starting material" shown in Table 1 below, prior to the addition of the Nd dopant. The composition specified in the above and the final composition specified as "final material" after the addition of the Nd dopant. In some instances, the magnet may have a high energy. [Table 1]
[0115] In one example, a magnet having the properties shown in FIG. 7 may include 3 at % Dy dopant. The starting material for the magnet was as shown in Table 2 below, prior to the addition of the Dy dopant, as "Starting Material". The composition specified, and the final composition after the addition of the Dy dopant, specified as "Final Material" In some instances, the magnet may have a high coercivity. [Table 2]
[0116] In some examples, the magnet compositions identified in Tables 1 and 2 have a composition of about 0.009 to about 0.08 a In some instances, the magnets identified in Tables 1 and 2 may have an accuracy of up to 10%. The dopant may be included in an amount of 0.1 to 100 μm.
[0117] Grain boundary engineering will not be limited to a thickness of about 6 mm of the magnet sintered body. For example, has performed grain boundary engineering to form sintered magnets having a thickness of about 6 mm or greater. In some examples, the thickness of a magnet formed using a grain boundary engineering process may be: It is at least 6mm thick.
[0118] Figure 8 shows the GBE processed sintered magnets with different amounts of Dy addition to Nd-Fe-B type sintered magnets. For example, the GBE technology described herein can be applied to large-scale sintered magnets. and adding 0.5 at% additive material, 2.0 at% additive material, or 3.0 at% additive material. In addition, by achieving the properties shown in FIG. 8, the remanence and coercivity can be improved. do.
[0119] FIG. 9 is an example of a process 900 for applying grain boundary engineering techniques. The present invention may be implemented using one or more of the above systems.
[0120] At 902, the process forms a cast alloy flake. For example, the GBE system The gold, pure elements, or both are melted and the molten alloy is poured onto a water-cooled copper wheel. The cast alloy flakes are formed from a plurality of 2:14:1 phase grains, e.g., NdFe 14 Contains B1 phase grains. In some examples, each of the cast alloy flakes includes 2:14:1 phase grains. In the present invention, a portion of the cast alloy flakes contains 2:14:1 phase grains, and a portion of the cast alloy flakes contains a) other b) particles containing materials other than Nd, Fe, or B, such as contaminants, or b) Nd of different composition -Fe-B, e.g., Nd2Fe 14 Contains grains other than B1.
[0121] Used in the alloys separately as pure elements or as a combination of alloy and pure elements The element combinations include: (i) Nd, Pr, Fe, FeB, and B; (ii) Nd, Fe, Co, Cu, and Dy; (iii) ) Nd, Fe, Co, Cu, Dy, a composition having a ratio of Nd75:Pr25, a composition having a ratio of Dy80:Fe20, and Pr, (iv )NdFe 14 B, (v) DyFe 14 B, (vi) PrFe 14 B, (vii) TbFe 14 B, (viii) NdCo 14 B, ( ix) Pr2Co 14 B, (x)Tb2Co 14 B, (xi) Nd2Ni 14 B, (xii) PrNi 14 B, (xiii) Tb2Ni 14 B. (xiv)V2FeB2, (xv)NbFeB, (xvi)MoFeB, (xvii)ZrFeB, (xviii)TiFeB, (xix) Nd-rich, (xx) CoNd3, (xxi) NiNd3, (xxii) GaNd, (xxiii) Nd oxide, (xxiv) Pr (xxv) RE carbides, (xxvi) Nd oxyfluorides, (xxvii) Re nitrides, or (xxvi ii) may include a combination of two or more of these. In some implementations, Some or all of the elements may come from waste magnet material. Some or all of this may be new magnetic fields not previously used in consumer products, for example. It is derived from sexual materials.
[0122] At 904, the process crushes the cast alloy flakes to form an initial powder. For example, the GBE system may be a jet mill processing system or another suitable system, e.g., A Cast alloy flakes using high-energy milling under r or He or another inert gas. In some implementations, the GBE system may be mixed with the powder for about 20 to 30 minutes. The cast alloy flakes are subjected to a temperature of about 150° C. and a pressure of about 1 to about 10 bar (about 0.1 to about 1 MPa) at a maximum. The cast alloy flakes may be thermally cracked by exposure to hydrogen gas. The GBE system maintains 2:14:1 phase grains, or approximately 90-97 vol% of these grains.
[0123] At 906, the process includes aligning and pressing the initial powder to form an initial compact. For example, the GBE system forms a pressed body from the starting powder.
[0124] In some implementations, a portion of the boron from the starting elements is converted to boron during processing of the alloy, e.g. , preparation and formation of cast alloy flakes, production of initial powders, production of initial compacts, or any of the above. In some implementations, during processing of the alloy, , oxygen, carbon, or both may be mixed with the powder. For example, the alloy may initially be Nd 14.2 Fe 79.3 B 6.5 (at%), and the initial compact may be Nd 14.2 Fe 79.55 B 6.1 C 0.05 O 0.1 (at% In some instances, the alloy may initially be Nd 31.284 Fe 67.6427 B 1.0733 (wt %), and the initial compact may be Nd 31.2275 Fe 67.7335 B 1.0054 C 0.0092 O 0.0244 (wt% ) may be.
[0125] At 908, the process sinters the initial compact. For example, the GBE system may first A fully dense sintered magnet is produced from the compact. In some implementations, during sintering: Oxygen, carbon, or both may be added to the initial compact. For example, the GBE system Lubricants may be added to the initial compact during or as part of the sintering process. Often, oxygen, carbon, or both may be added to the initial compact as a result of the lubrication. In some examples, the sintering process may include the use of argon gas. The oxygen present in the oxygen gas may be added to the initial compact, for example during sintering.
[0126] The GBE system performs steps 902 through 908 to produce a sintered magnet having a plurality of 2:14:1 phase grains. The sintered magnet may then be processed using steps 910 to 918, described below, to The 2:14:1 phase grains of the sintered magnet may be maintained in the final product. For example, the process 900 may include, in step 908: All of the 2:14:1 phase grains formed within the cast alloy flakes in fully dense sintered magnets produced in the or about 90-97 vol %, and may be subjected to step 910, which is described in more detail below. All or about 90 to 97 vol of 2:14:1 grains from fully dense sintered magnets in the powder produced in % can be maintained.
[0127] In some instances, the GBE system may be used to develop new magnets, e.g., 9. Accept magnets that have never been used or have been used infrequently, step 902 The GBE system processes the magnet instead of performing steps 902 to 908. Instead, any suitable type of sintered magnet may be used.
[0128] At 910, the process places the magnetic material in a mixing device to create a powder. The magnetic material may be exposed to a pressurized hydrogen atmosphere for a given period of time, temperature, rotation speed, etc. For example, the magnetic material may be placed in a hydrogen mixing reactor as shown in FIG. 2, FIG. 3G, or both, or in another suitable The GBE system, e.g., a mixer, may be used to process the powder. In particular, the 2:14:1 phase grains from the magnetic material are maintained at about 90 to 97 vol. % or all of them. In some implementations, when the GBE system produces powder from an initial sintered magnet, the GBE system The stem removes the old Nd-rich grain boundary phase from the original sintered magnet.
[0129] In some examples, the rare earth transition element additive material is added to the magnetic material before or after mixing. In some implementations, Nd—Fe—B magnets, e.g., magnetic materials and rare earth metals, may be added. Earth element additives, e.g. Nd 1-x Pr x The materials were mixed together in a mixing device at a ratio of 99.9:0.1 to 81:19 at%. In some instances, the rare earth transition metals are mixed together in situ. The ratio of magnetic material to transition metal additive material is 99.9:0.1 to 94:6 at%. In particular, 99.9:0.1 to The 99:1 at% ratio is mixed together uniformly. The rare earth and transition element additive materials are separately cut into pieces. The ferromagnetic material may be added to the magnetic material after step 910.
[0130] For example, the GBE system uses Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% rare earth and transition element addition Additive: Nd2Fe 14 It may be mixed with powder B to form a composite powder and, optionally, sintered. The old Nd-rich grain boundary phase that is normally present in the body of an Nd-Fe-B magnet is 11.92 Dy 42.32 Co 38. 39 Cu 5.34 Fe 2.03 In some examples, the GBE system may be replaced with N d 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The precursor was prepared by flash pyrolysis of the fine powder (at%). The precursor is then converted into NdFe 14 It may be mixed with powder B to produce a composite powder. For example, fine Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% particles of Nd2Fe 14 In B powder A hydrogen mixing reactor may be used for the first mixing step of dispersion.
[0131] In some implementations, the GBE system comprises the Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at % rare earth transition element additive material, for example, the precursor is subjected to arc melting, RF (radio frequency) , bookmolding, strip casting, or atomization, or any other suitable method. In some instances, Nd 11 .92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The elements in the precursors that produce the at% rare earth and transition element additive materials The purity level of elements, e.g., Nd, Dy, Co, Cu, and Fe, should be 95% or higher, e.g., 99.9% purity. be.
[0132] In some instances, the GBE system may incorporate a melt preparation process, such as vacuum induction melting. For example, the GBE system may include at least All contain copper, cobalt, iron, and one or more modifier elements, such as neodymium, praseodymium, di Multicomponent highly alloyed materials containing sprosium, terbium and combinations of two or more of these Vacuum induction melt preparation of materials may be used. GBE systems use alloyed materials to It can replace the Nd-rich grain boundary phase present in sintered magnets.
[0133] For example, the GBE system may be used to heat, for example, high density crucibles in alumina or zirconium crucibles. In a crucible, high purity crucible, or high density high purity crucible, the alloy elements, e.g., Nd, Pr, Fe, Dy , Tb, Co, and Cu may be melted to prepare a compound of the elements, for example, five elements. Some examples of such compounds include Nd2Dy7Co6CuFe 0.33 , Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at%, Pr 11.92 Tb 42.32 Co 38.39 Cu 5.34 Fe 2.03 at%, or Pr2Tb7Co6CuFe 0.33 are mentioned See, for example, Tables 3 and 4. For example, Nd element can be replaced by Pr, The Dy element can be replaced by Tb.
[0134] The GBE system melts the elements at 1450° C. to produce a molten alloy, and the molten alloy material The alloy is poured from an alumina or zirconia crucible onto a water-cooled copper wheel to produce cast alloy flakes. In some instances, the GBE system cools the molten alloy in the crucible to room temperature. The GBE system may be used to prepare blocks from compounds, for example, 10 5 Kelvin / second to produce a strip cast alloy flake; For example, flakes less than 50 micrometers in size may be achieved. If the E system cools the molten alloy slowly, the GBE system , the temperature may be cooled at a rate of 10 to 100 Kelvin / second.
[0135] The GBE system may be configured to mix the elements in an Ar atmosphere at, for example, an absolute pressure of approximately 1.5 bar (150 kPa). It may be melted under pressure or in another inert gas, such as nitrogen. In an example, the GBE system allows the elements to be melted in a vacuum. For example, the GBE system can be used for compound melting and annealing for rare earth transition element additive material alloys. If an inert gas or vacuum is used during preparation, the GBE system will reduce the amount of oxygen in the alloy. In some instances, the GBE system may slightly increase the phosphate content, carbon content, or both. If the GBE system uses an inert gas or vacuum during melting and preparation of the compound, The alloy may be made of neodymium, dysprosium, praseodymium, or any combination of two or more of these elements, e.g. For example, evaporation losses may be reduced.
[0136] In some implementations, the GBE system is at least 400V, 3000Hz, and 100KW of power. The GBE system may use an induction melting process with a charge size of 55 kg. The inert atmosphere used during melting of the matrix may contain an effective amount of a reducing agent, for example: The GBE system may use hydrogen as a reducing agent. In some examples, the GBE system The elements were stirred in a perforated crucible by argon purging from the bottom of the crucible. To achieve a uniform distribution of the elements in the melt,
[0137] The GBE system can be used to prepare the compounds as described above, for example to prepare other alloys. Reduce the amount of O, C, or both introduced into the rare earth transition element additive material compared to conventional techniques. The GBE system replaces some or all of the Nd-rich grain boundary phase with the liquid eutectic phase of the alloy. This can improve the properties of the final sintered magnet body. [Table 3] [Table 4]
[0138] In some implementations, the GBE system performs an arc melting process, e.g., vacuum melting or The rare earth transition element additive material may be prepared using, for example, GBE series. The stem is a copper crucible that is heated, for example, by induction heating, in a copper crucible, with the elements for the alloy, such as the elements mentioned above. The GBE system melts the alloy using melting or arc melting under vacuum to produce a molten alloy. The copper crucible is cooled, for example by water cooling, to form a melt which solidifies continuously from the bottom upwards. The GBE system melts the elements to produce the molten alloy. The GBE system may be configured to produce a molten alloy having a melting point of 1.8 volts and a melting point of 1.8 volts. The elements may be melted under an absolute pressure of about 180 kPa, for example in an argon atmosphere. The GBE system is 10 -1 The molten alloy may be cooled in a vacuum of greater than 10 bar (10 kPa). .
[0139] In some instances, the GBE system heats the ingot using arc melting. and remelting the ingot in the copper crucible to produce a remelted molten alloy. The GBE system cools the remelted molten alloy and solidifies it continuously from the bottom up. A solid remelted ingot is produced.
[0140] The arc melting or remelting process requires high Br of 1.3 T or more and high insulation of 2000 kA / m or more. The present invention provides a rare earth sintered magnet having a modified grain boundary phase and specific properties such as magnetism, magnetoresistance, or both. The GBE system can produce high performance alloys, high purity alloys, or high performance high purity alloys for manufacturing. The melting or remelting process can be used to reduce gas content, e.g., contamination, macrosegregation. and reduced microsegregation, increased yield, improved reproducibility of properties, or two or more of these. For example, the GBE system can limit the pool of molten metal alloy that is created during remelting. This allows the solidification rate of the ingot, e.g., segregation, and the chemical composition of the molten metal alloy to be controlled. This allows for control by the GBE system, which can improve the reproducibility of properties.
[0141] In some instances, the GBE system uses RF melted ingots to produce Nd 11.92 Dy 42 .32 Co 38.39Cu 5.34 Fe 2.03 % precursor, and the molten ingot is naturally, e.g. The GBE system can be cooled in an alumina crucible at room temperature, without a cooling source, or both. The system is pre-heated to ensure uniform elemental distribution in the molten ingot. The ingot may be melted multiple times, for example, twice. Inductively Coupled Plasma (ICP) may be used to confirm the distribution of elements in the final precursor. 11.92 Dy 42.32 Co 38. 39 Cu 5.34 Fe 2.03 The density of the precursor at% is 8.21 g / cm 3 The GBE system can be The density of the precursor may be ascertained using the principles of lattice.
[0142] In some implementations, the GBE system uses a free-falling Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 A spray atomizer with high velocity gas injection into a stream of at% melt was used to The precursor may be formed from a rare earth transition element additive material. For example, the high velocity gas Gas injection is performed with an inert gas, e.g., Ar, Ne, He, N, or a combination of two or more of these. The gas may have a velocity of 500 m / s or may have a velocity of 500 m / s, or may both. The injection is performed on the free-falling Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The flow of the melt is Each of the droplets (s The granulocyte may fragment into granulocyte pellets (malleolar droplets).
[0143] The high velocity gas jet causes the droplets to form, propel and cool, forming an almost spherical shape. Droplets with particle sizes of submicrons and microns can be produced, which allows for high surface area Nd with volume-to-volume ratio 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% particles can be produced. For example, the GBE system uses this particle to 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% precursor and the NdFe 14 B powder or Nd2(FeCo) 14 Composite powder was produced using powder B. Good. 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The process for preparing the appropriate powder size is , not limited to spray atomization, spray pressurized atomization, two-fluid atomization, rotary atomization This can also be achieved by atomization, foam atomization, electrostatic atomization, ultrasonic and whistle atomization.
[0144] FIG. 10 shows an example of a spray atomizer 1000, which has a bottom opening. The molten Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The at% precursor 1002 falls For example, the molten precursor 1002 may be a free-falling Nd 11.92 Dy 42.32 Co 38.39 Cu5 .34 Fe2.03 Inside high-velocity gas jets of, for example, 0.18 to 0.58 MPa against at% melt flow The high velocity inert gas jet 1006 can then be used to spray a volume of Molten Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The at% precursor 1002 is rapidly fragmented into numerous droplets. The droplets have a maximum oxygen concentration of 0.04 wt%, a loss of about 2 wt% of rare earth material, and a melting point of 140 to 200 nm. The precursor may have a powder size of 280 micrometers. 11.92 Dy 42.32 C o 38.39 Cu 5.34 Fe 2.03 The density of the at% powder is 8.08 g / cm 3 In some examples, The droplet density varies from 95 to 98% of the theoretical value, e.g., single-phase Nd 11.92 Dy 42.32 Co 38.3 9Cu 5.34 Fe 2.03 At% droplets: 8.375 g / cm 3 It was.
[0145] The GBE system then transfers the atomized powder or molten droplets to the Nd2Fe 14 B Sintered block with water The hydrogen mixing reactor may be evacuated and then mixed with the hydrogen to produce a complex mixture. Then, hydrogen gas is introduced into the precursor and the NdFe 14 B sintered block is placed in the processing chamber. Hydrogen may be introduced for a period of time. 11.92 Dy 42.32 Co3 8.39 Cu 5.34 Fe 2.03at % precursor, e.g., powder or droplets, or both, are absorbed by the corresponding This causes the material to expand and the corresponding material to break down into a powder, e.g. a coarse powder. Processing in a hydrogen mixing reactor is Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% precursor, fine particles In some instances, the hydrogen-mixed reaction releases trapped gases accumulated during the polymerization process. The reactor is maintained at approximately 2 bar (approximately 200 kPa) until completion of the process, at which point no change in pressure is detected. The precursor and the N are mixed under the absolute pressure of a) while constantly supplying hydrogen into the processing chamber. d2Fe 14 The GBE system may then process the powder in situ at 58 Heat to 0°C and combine Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 Partially mixed with at% / Nd-Fe-B mixture The hydrogen may then be desorbed, for example, from the bulk of the powder particles. The system transfers the composite powder into an argon atmosphere transfer box, e.g. It may be moved to another component of the GBE system.
[0146] In some implementations, the GBE system comprises a composite powder, e.g., Nd 11.92 Dy 42.32 Co 38. 39 Cu 5.34 Fe 2.03 The precursor and Nd-Fe-B or Nd-Fe-Co-B are milled with high energy. Further processing may be performed using ball milling or jet milling. The powder is mixed until the composite powder becomes a homogeneous mixture and has a powder size of 2 to 4.5 μm. It may also be processed.
[0147] The rare earth transition element additive material contains one or more of the elements Nd, Pr, Dy, Co, Cu, and Fe. Some examples of ranges of elemental additive material combinations are: Nd:[6.1717,11.8917 ](at%);Pr:[1.5495,4.821](at%);Dy:[0.2132,5.3753](at%);Co:[0,4. 0948](at%); Cu: [0.0545, 0.2445](at%); and Fe: [81.1749, 85.867](at%) In some implementations, the amount of rare earth element in the rare earth transition element additive material is The range of can be [13.236, 16.407] (at%) or [28.82, 33.7] (wt%). In some instances, small amounts of O, C, or both may be added during processing of the rare earth transition element additive material. The rare earth transition element additive material may be added. :Nd:[12.726,24.85](wt%);Pr:[3.1638,9.677](wt%);Dy:[0.506,12.49] (wt%);Co:[0,3.4963](wt%);Cu:[0.0506,0.2248](wt%);and Fe:[63.6551 , 70.009] (wt%).
[0148] In some examples, the GBE system may be modified to remove old Nd-rich grain boundary phase by any suitable method. The Nd-rich grain boundary phase is oxidized and replaced with rare earth transition element additive materials. Therefore, if there is no reaction with H2 during hydrogen processing, the GBE system will 14 B powder is sieved. In some examples, the GBE system may include: The Nd2Fe 14 The B powder is sieved to obtain nanometer sizes, e.g., less than 1 micrometer. In some implementations, ultrafine particles including Nd-rich grain boundary phase particles may be removed. In addition to the rare earth and transition element additive materials, the GBE system also uses Nd2Fe 14 B Fragmenting of sintered magnets Thus, some of the additive material may not need to be removed during the sieving process.
[0149] The rare earth transition element additive material is determined based on elemental analysis of the magnetic material composition and a predetermined Determined by experiment and estimation to be suitable for achieving the target formulation and magnetic performance The formulation may be selected using a database of formulations, or by any other suitable method. For example, the database may include information on the properties of the resulting sintered magnet product to achieve desired properties. A magnetic material and a rare earth transition element additive material added to the magnetic material are shown in the past. The data may include:
[0150] In some examples, the system may be constructed, for example, in step 918, using the following formula: For example, the final amount of Nd in the sintered magnet product may be determined. The value f1 is w = [81, 99.9] (at%), 1-w = [0.1, 19] (at%), and p1 is the value of the initial alloy. When the amount of Nd and a1 are the amounts of Nd in the element additive material, f1=w×p1+(1-w)×a1. The final value f2 of Pr in the sintered magnet product is given by: In this case, f2=(1-w)×a2. The final value of Dy in the sintered magnet product, f3, is determined by the elemental additive, a3. If it is the amount of Dy in the material, then f3=(1-w)×a3. The final value of Co in the sintered magnet product f4 can be f4=(1-w)×a4, where a4 is the amount of Co in the elemental additive material. The final value of Cu in the magnet product, f5, is calculated as f5=(1-w The final value of Fe in the sintered magnet product, f6, can be calculated by multiplying p2 by the amount of Fe in the initial alloy. Therefore, if a6 is the amount of Fe in the elemental additive material, then 6 = w × p2 + (1-w) × a6. The final value of O in the magnet product, f7, is calculated by dividing p4 by the amount of O in the initial alloy, for example, after processing of the alloy. a7 is the amount of O in the elemental additive material, and E_O is the amount of O in the combined alloy and The amount of oxygen added during processing of the elemental additive material to produce the sintered magnet product. In this case, f7=w×p4+(1-w)×a7+E_O. The final value f8 of C in the sintered magnet product is p5 is the amount of C in the initial alloy, for example after processing of the alloy, and a8 is the amount of C in the elemental additive material. and E_C is a quantity of C obtained by processing the combined alloy and elemental additive material to obtain said If it is the amount of carbon added during the preparation of sintered magnet products, f8=w×p5+(1-w)×a8 +E_C. The final value f9 of B in the sintered magnet product is the amount of B in the initial alloy, p3 is the amount of B in the initial alloy. In this case, f9 = w × p3.
[0151] In some examples, the final value f1 of N is in the range of [7.3635, 11.1038] (at%). The final value of Pr, f2, can be in the range of [1.445, 3.6323] (at%). The final value of Dy, f3 can be in the range of [0.199, 4.0535] (at%). In some implementations, the rare earth The total amount of rare earth elements in the transition element additive material is in the range of [12.66, 15.03] (at%). The final value of Co, f4, can be in the range of [0, 3.098] (at%). The final value of Cu, f5, can be in the range of [ The final value of Fe, f6, can be in the range of [76.3928, 80.0287] (at%). The final value of O, f7, may be in the range of [0.09, 4.0] (at%). The final value of C, f8, can be in the range of [0.01, 1.0] (at%). The final value of B, f9, can be in the range of [5.7 493, 6.4244] (at%).
[0152] In some examples, the final value f1 of N is in the range of [16.125, 24.575] (wt%). The final value of Pr, f2, can be in the range of [3.125, 7.75] (wt%). The final value of Dy, f3, can be In some implementations, the rare earth transition element The total amount of rare earth elements in the additive material may be in the range of [29, 33] (wt%). The value f4 can be in the range of [0, 2.8] (wt%). The final value f5 of Cu can be in the range of [0.05, 2.8] (wt The final value of Fe, f6, can be in the range of [64.6705, 69.2205] (wt%). The final value of O, f7, may be in the range of [0.01, 0.9] (wt%). The final value of C, f8, may be The final value of B, f9, can be in the range of [0.01, 0.5] (wt%). It may be within a range.
[0153] At 912, the process includes fragmenting and uniformly mixing the powder by any suitable means. In some implementations, this involves granulating the granules to a target particle size of about 1 to about 4 microns. This can be accomplished by wet milling. Any suitable fragmentation device can be used, such as those described in more detail above. The powder may be fragmented, homogenized, or both using any of the techniques described above. In some implementations, steps 910 and 912 may be performed simultaneously. Instead of adding a small fraction of the rare earth transition element additive material to the batch being hydrogenated, the The rare earth material may be hydrogenated separately and mixed at 912. The rare earth transition element additive is milled separately, and after milling the magnetic material, e.g. , preferably well divided, and using high pressure, e.g. 60 bar (6 MPa), The powder may be added after 912 to form a powder in the range of about 50 microns.
[0154] In some implementations, the GBE system may use, for example, a hydrogen mixing reactor followed by: A jet mill processing system was used to produce composites with resulting powder sizes ranging from 2 to 4.5 μm. The powder may be homogenized and formed.
[0155] In some implementations, the GBE system includes a Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% powder End, Nd2Fe 14 B powder to produce a bulk Nd-Fe-B body, e.g., the final sintered magnet. In some cases, the GBE system achieves a uniform distribution of the new grain boundary element concentrations within the grain boundary. By using homogenization and uniform distribution, the final sintered magnets derived from different initial sintered magnets can be more It may also be uniform.
[0156] In some instances, homogenization involves a reduction in grain size, e.g., grain size of the original Nd—Fe—B powder. , Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 Surrounding, e.g., by at% powder, or In some implementations, homogenization is performed when the GBE system is 11.92 Dy 42.32 C o 38.39 Cu 5.34 Fe 2.03 The coarse powder of 1 at% and the initial coarse powder of Nd-Fe-B sintered magnet were subjected to mechanical force. For example, H2 may be added to the material to form small particles having a size of, for example, about 0.5 μm to about 5 μm. The mechanical force may include a grinding step of grinding the material, e.g., Nd 11 .92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 By adding at% and Nd-Fe-B sintered magnet, the material The particles can be made from, and the surface area of the particles can be increased. In the example, the homogenization is performed using NdFe 14 Within the B particle, Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% This can result in a random distribution of particles. In some instances, the GBE system uses NdFe 14 Nd in B powder 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The distribution of at% powder was measured using a spiral mixer. V-type blender or twin shell V-type blender, jet milling, ball milling using mechanical mixing devices including milling, high energy milling, or in a hydrogen mixing reactor Homogenization may be accomplished using a mechanochemical device such as.
[0157] At 914, the process further comprises: For example, the GBE system screens larger particles, e.g., about 500 microns, from the collected material. The oxidized fraction of the powder is treated by sieving out particles of about 100 to about 2 mm from the fine powder. This technique is advantageous because the oxide is harder than the main fraction of the rare earth magnet material being recovered. This prevents the oxidized particles from being fragmented into smaller pieces. For example, hydrogenation, milling, jet milling, etc., are effective in removing the oxidized fraction. Milling, crushing, or other suitable methods may be less prone to decomposing the oxides. By increasing the size distribution of the particles and eliminating the proportion of oxides in the fine powder by sieving, or can be reduced.
[0158] At 916, the process includes filling a press and establishing a magnetic field within the press. The fine powder is pressed and aligned to form a green compact, and The process then involves sintering and heat treating the green compact to form the final sintered magnet product. For example, the GBE system is designed to deposit the above-mentioned Cr-Al-Al-Si alloy in the grain boundaries between the 2:14:1 phase grains that were initially formed in the cast alloy flakes. A green compact is prepared in which a rare earth transition element additive material is present. The rare earth transition element additive material is The 2:14:1 phase is uniformly distributed among the grains. The final sintered magnet product has a high density, e.g., 7.5-7.6 g / cm 3 It may be a complex of:
[0159] The rare earth transition element additive material may be, for example, substantially Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 a % of the new grain boundary phase. In some implementations, the new grain boundary phase may be formed at a grain boundary of about 100 μm to about 100 μm. The initial grain boundary phase previously contained in the initial sintered magnet is substantially replaced. For example, The Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The grain boundary phase at% essentially replaces the old Nd-rich grain boundary phase. The new grain boundary phase may have increased grain boundary cohesion with increasing volume fraction; and the formation of reversed nucleation sides in the final sintered magnet product. In some instances, the new grain boundary phase may act as a nucleation site for growth. , which can reduce the possibility of surface defects on individual grains of the final sintered magnet.
[0160] In some implementations, the GBE process uses a powder mixing and hydrogen mixing reactor. , NdFe 14 B alloy and Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 After preparing the at% composite mixture The GBE process may remove Nd-rich phases from the alloy. 11.92 Dy 42.32 C o 38.39 Cu 5.34 Fe 2.03 At% is used as the rare earth transition element additive material, and a new grain boundary phase By increasing the volume fraction from 10 to 90 vol%, the new grain boundary phase exhibits improved density. In some examples, the rare earth transition element additive material may be , making the sintering process more efficient and imparting better mechanical properties to the final sintered magnet. For example, sintering may be performed in the range of 10-30 vol.% and 50-90 vol.% of the grain boundary phase, or both. In some examples, the GBE system may use the GBE process. When a new grain boundary phase is added to the final sintered magnet by the addition of the grain boundary phase, the final sintered magnet has improved corrosion resistance. Yes.
[0161] For example, Figure 11 shows the comparison of GBE final magnets with other Nd-Fe-B magnets, e.g., waste sintered Nd-Fe-B magnets. For example, FIG. 11 shows a graph comparing the corrosion resistance of the following sintered magnets: (a) 1 at% Nd / Pr Final GBE with added Nd-Dy-Fe-Co 0.78 -B magnet, (b) Nd-Dy-Fe-Co 0.9 -B magnet, (c )Nd-Dy-Fe-Co 0.7 -B magnet, (d) Nd-Dy-Fe-Co 0.5 (f) Nd-Fe-B magnets, and (f) Nd-Fe-B sub-magnets. Surface area of conventional magnet: 1cm 2 The weight loss in milligrams per unit mass is shown. Highly accelerated stress tests were conducted at 130°C and 2.7 bar (270 kPa) in water vapor, similar to those of 2-66. The magnet was tested for its dependence on Co concentration with an exposure time of 20 days.
[0162] The GBE system added unused additive materials to waste Nd-Fe-B powder to recover it. The GBE final magnets were produced with the magnetic properties, microstructure, and density. is, for example, Nd and Pr, or Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe2.03 at%, or Nd and two types The additional material may be Fe, Co, Cu, Dy, Nd, or Pr and two additional materials. Pr, or Pr. The GBE final magnet shows improvement over other magnets tested. In this example, the corrosion resistance is achieved by using a newly modified Nd 11.92 Dy 42.32 Co 38 .39 Cu 5.34 Fe 2.03 At% grain boundary phase is included at 10vol% and replaces the old Nd-rich grain boundary phase. begins to increase.
[0163] In some implementations, the initial sintered magnet, e.g., waste Nd-Fe-B sintered material or freshly The starting composition of the sintered magnet is 5.585wt% Pr, 23.615wt% Nd, 0.4wt% Dy, and 0. 79wt%, Cu at 0.1wt%, B at 0.98wt%, C at 0.0704wt%, O at 0.059wt%, and Fe The final composition of the final sintered magnet may be 5.22 wt% Pr, 68.4006 wt% Nd 22.88wt%, Dy 0.93wt%, Co 1wt%, Cu 0.12wt%, B 1wt%, C 0.13wt% % by weight, O at 0.12 wt%, and Fe at 68.6 wt%.
[0164] In some implementations, the GBE system can design appropriate grain boundary engineering techniques. For example, the GBE system provides global trend information on the degree of equilibrium of disordered and ordered grain boundaries. By using the zeolite, the overall grain size is reduced by grain boundary segregation engineering, and the grain boundary energy and grain boundary mode are improved. In some instances, the GBE system may lead to a reduction in As starting information for grain boundary segregation and microstructural information for grain growth inhibition, the crystallographic Analysis and elemental analysis, or intragranular and adjacent Nd2Fe 14 New grain boundary between B grain boundaries Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 quantification of total addition in at% volume fraction, or both. In some implementations, grain boundary engineering is performed throughout the entire final magnet body, e.g., throughout the grain boundaries. Barrel Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 This results in a uniform distribution of the at% precursor powder.
[0165] In some implementations, the GBE system includes a process 900, Some or other suitable methods may be used to modify the grain boundaries of other types of magnets. For example, the GBE system is Nd2(FeCo) 14 B sintered magnet or Sm2Co 17 The grain boundaries of sintered magnets may be modified. In some instances, Sm2Co 17 When modifying the grain boundaries of sintered magnets, the GBE system uses Sm Combinations of one or more of the following elements may also be added: Co, Zr, Fe, or Cu.
[0166] Example 2 Magnets made using GBE technology have improved temperature performance. Magnets made with this method have improved thermal stability and improved magnetic performance. Regenerated magnets are made from end-of-life products such as Nd-Fe-B renewable materials. Improved magnetization compared to the input material processed to produce the magnet, e.g., first-use magnet. Thermal stability. Input first or nearly first Nd-Fe-B magnetic material. Magnets made from and processed using GBE technology are significantly better than magnets made using other processes. In comparison, it may have improved thermal stability.
[0167] Table 5 shows two starting magnets, Starting Magnet 1 and Starting Magnet 2, and the magnets produced from the starting magnets. The ICP compositions of the two final magnets, Final Magnet 1 and Final Magnet 3, are shown. Final Magnet 1 uses GBE technology. The final magnets 2 and 3 each contained an addition of 0.5 at % of additive material added using GBE. This includes the addition of 2 at % and 3 at % of additive material added using techniques.
[0168] Starting magnet 1 was used as the starting magnetic material for the final magnet 2 with the addition of 2 at% and The starting magnet 2 was used as the starting magnetic material for the final magnet 3. Starting magnets 1 and 2 were made from the first magnetic material, i.e. , it was not a regenerative magnet. [Table 5]
[0169] Tests were performed to determine the thermal stability of the starting and final magnets (i.e., from 20 to 200°C). Each magnet has a cylindrical shape and a length / diameter ratio L / D of 0.9 cm / 1 cm = 0.9. For example, the length / diameter ratio L / D of each magnet was the same. The magnets are placed in a magnetic permeability meter and the remanence and coercivity of each magnet are measured at room temperature. The test involves increasing the temperature and holding it at each stage for 15 minutes, then measuring the residual strength of each magnet again. This was followed by measuring the retention and coercivity.
[0170] Starting magnet 1 and starting magnet 2 have a sharp bend in the demagnetization curve, i.e., the residual magnetism abruptly drops to zero. The final magnet 1 had a point where the magnetization curve dropped to just above 80°C. The final magnet 3 had a steep bend in the demagnetization curve at over 200°C. These results show that both Final Magnet 1 and Final Magnet 3 have the same temperature as the starting material 1. and 2, and the final magnet 3 is the most thermally stable of the four magnets tested. It is the most thermally stable of the three.
[0171] The reversible loss coefficients α and β plotted against temperature indicate the reversible loss coefficients that a magnet operates at at a particular temperature. For example, Table 6 below shows the reversible decrease in remanence and coercivity over the temperature range The reversible decrease α of the coercive force and the reversible decrease β of the coercive force of the starting magnet 1 and the final magnet 3 are summarized. . [Table 6]
[0172] The magnetic flux φ of the magnet decreases by only 5% while it is held at temperature and during cooling. is the temperature at which the reaction remains reversible, T 5% To determine the temperature of a magnet, the magnet The magnetic flux readings of the magnet were obtained after holding it at various temperatures ranging from 20 to 200°C for 2 hours. When the final magnets 2 and 3 were tested, both magnets were found to have a low magnetic flux at 200°C. The maximum temperature T 5% had the following characteristics:
[0173] 12A and 12B show the reversible decrease α in remanence of the starting and final magnets. For example, FIG. 12A shows the reversible decrease α of the remanence of starting magnet 1, final magnet 2, and final magnet 3. For example, final magnet 3 has a better α compared to starting magnet 1 at each temperature range, and The improvement ranges from 84% at 80°C to 25% at 200°C. The final magnet 2 has The starting magnet 2 had an improved α compared to the starting magnet 1. FIG. 12B shows the residuals of the starting magnet 2 and the final magnet 1. The final magnet 1 exhibits a reversible decrease in magnetism α over the temperature range compared to the starting magnet 2. It had a pronounced α.
[0174] 13A and 13B show the reversible decrease β in coercivity of the starting and final magnets. Final Magnet 1 has a β that decreases as temperature increases. For example, as temperature increases, The decrease in magnetic force reaches saturation.
[0175] For example, FIG. 13A shows the reversible decrease β in coercivity of starting magnet 1, final magnet 2, and final magnet 3. FIG. 13B shows the reversible decrease β in coercivity of the starting magnet 2 and the final magnet 1. Stones 2 and 3 showed improved values of β at each temperature when compared to the starting magnets. The final magnet 3 has a better β in each temperature range compared to the starting magnet 1, and the improvement is , ranging from 26% at 80°C to 6% at 200°C.
[0176] Final magnet 1, final magnet 2, and final magnet 3 have an overall improvement in coercivity (iHc) value. For example, the final magnets 1, 2, and 3 across the temperature range compared to their respective starting magnets. The average coercivity (iHc) improvements for samples 1 and 2 are 16%, 70%, and 128%, respectively.
[0177] Table 7 shows the reversible relationship between Nd-Fe-B magnets made from virgin materials and recycled Nd-Fe-B magnets. The regenerated magnets have improved α and β compared to magnets made from virgin materials. Specifically, the regenerated magnets have a 10 times better magnet strength than magnets made from virgin materials. At 80°C, the regenerated magnet has a reversible decrease in remanence α. At 140°C, the regenerated magnet has a reversible decrease in remanence α from the original material. Reversible reduction of remanence in magnets made from α. Reversible reduction of remanence twice as good as α. has a proportional decrease α. [Table 7]
[0178] In some implementations, elemental additions are added to the magnetic material using the GBE process. The higher the temperature, the more thermally stable the resulting final product will be compared to the starting magnetic material. In some instances, the GBE process may be carried out using starting materials or other processes. Compared to magnetic materials, this can provide improved temperature stability and coercivity.
[0179] Example 3 In some instances, waste magnets may be processed using GBE techniques. The system may, for example, produce magnets using steps 902 to 908, which include producing waste magnets. In some instances, the waste magnets may be made using a different process or may be produced from a different system. It may also be obtained from the GBE system.
[0180] The GBE system processes the waste magnets using steps 910 through 918 described above. In the present invention, the waste magnets and regenerated magnets may have properties similar to those shown in Table 8 below. As mentioned above, the amount and type of elements contained in the additive material will determine the final magnetic material having the same properties. In some instances, the magnet may be adjusted to fit different types of waste magnets. , 1 at % Nd / Pr was added to the particles formed from each of the discarded magnets. [Table 8]
[0181] The remanence (Br) of the final magnet can be 1.25 T. The coercivity (iHc) of the final magnet can be 1710 kA. The final magnet energy product (BHmax) is 303 kJ / m 3 The final magnet The product is 7.55g / cm 3 The density of the sintered body may be 0.01 to 0.01.
[0182] Figure 14 shows, for example, a magnet made from mixed grade discarded magnets with 1 at% Nd / Pr mixture addition. 1 shows a graph of exemplary properties of the final magnet described in Example 2. For example, the final magnet may be The Nd / Pr grain boundary phase may replace the Nd-rich grain boundary phase.
[0183] FIG. 15 shows the magnetic properties of discarded sintered magnets and reclaimed magnets processed using, for example, the GBE process. Some examples of the functions are shown below. For example, multiple discarded sintered magnets are mixed together to form a single magnet with different element compositions. The magnets were collected from consumer products having the same composition (for example, ICP analysis of the discarded sintered magnets). (See Table 8 for details.)
[0184] In this example, the coercive force is the magnetic field strength of the magnet, e.g., both the discarded sintered magnet and the regenerated magnet. by the nucleation of so-called reverse domains at the surface defects of individual grains. The GBE system can add new grain boundary phases using, for example, Nd / Pr additive materials. The formation of these defects can be suppressed by the above-mentioned method. Here, the new grain boundary phase is formed by the following method: - It can surround Fe-B phase grains and minimize the occurrence of surface defects such as cracks, bumps, and pits. do.
[0185] In some implementations, the GBE system may discard the regenerated magnet as shown in FIG. It can be made to have a coercivity equal to or greater than that of sintered magnets. The coercivity of the starting magnet is about 1400kA / m, and the coercivity of the magnet processed using GBE is 170 For example, when forming a regenerative magnet, the following GBE process: a) Nd / Pr additive material Preparation of composite powder from raw materials and Nd-Fe-B waste magnets; b) Processing parameters, e.g., jet c) adjusting the milling, sintering parameters, and annealing; or c) both to obtain scrap magnets. The GBE system can restore or improve the coercivity of the Nd / Pr grains by forming new Nd / Pr grain boundary zones with more uniform NdFe 14 The shape of the inversion domain nucleation site when forming the encapsulation of B matrix phase grains By preventing the formation of magnets, the performance of recycled magnets can be improved compared to discarded sintered magnets. In this example, the GBE system uses a new Nd / Pr grain boundary phase to "Old" Nd nucleation sites that can act as nucleation sites for the formation and growth of inversion domains at This is accompanied by an increased volume fraction of the new Nd / Pr grain boundary phase. This is due to the increased grain boundary cohesion.
[0186] Example 4 In some implementations, when the GBE system uses a spray atomizer, the GBE The system initially measured a density of 8.375 g / cm 3and a single phase with a difference of about 95-98% from the theoretical value Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% powder may be used. The density is 8.08g / cm 3 Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% precursor was prepared. The GBE system then 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% precursor, e.g. For example, the pulverized powder may be NdFe 14 B sintered block to the hydrogen mixing reactor. A composite powder may be produced from the precursor and the sintered block.
[0187] For example, Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 Precursor and sintered block mixed with hydrogen After placement in the reactor, the hydrogen mixing reactor may be evacuated and then hydrogen may be introduced for 12 hours. Hydrogen is Nd2Fe 14 B sintered block and Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 at% precursor The powder expands and breaks the sintered block into coarse powder, and Nd 11.92 Dy 42. 32 Co 38.39 Cu 5.34 Fe 2.03 The at% precursor powder is further decomposed and accumulated during the atomization process. The hydrogen mixing process is carried out at an absolute pressure of about 2 bar (about 200 kPa). While constantly feeding hydrogen into the hydrogen mixing chamber, the mixing process is completed. The GBE system may then mix the powder in the hydrogen mixing chamber, e.g. Heating in situ up to 550° C. partially desorbs the composite mixture, e.g., the bulk of the powder particles. Hydrogen may be released from the
[0188] Example 5 In some implementations, the final magnet product produced using the GBE process may be manufactured using other magnets. For example, it may have improved temperature stability compared to other regenerative magnets. For example, the GBE system For example, the team used a hydrogen mixing process to create powder from Nd-Fe-B material and then mixed the powder with Nd1 1.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At%, the old Nd-rich grain boundary phase is mixed with new Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 The powder and the Nd 11.92 Dy 42 .32 Co 38.39 Cu 5.34 Fe 2.03 The mixing of Nd-Fe-B powder with at% results in new Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 At% grain boundary phase can be homogenized, while the old Nd-rich grain boundary phase For example, sieving, air blowing, vibration, shape separation, density gradient separation, twin cylinder The solids are removed by gravity separation, or a combination of two or more of these.
[0189] The GBE system includes a step of obtaining a composite raw powder and subjecting the composite raw powder to a magnetic field, e.g. Orientation may be performed in the inter atmosphere under magnetic field. While orienting, the GBE system compresses the powder and applies the magnetic field to form a compact. The GBE system may sinter the shaped composite body to produce a final sintered magnet product. You may get it.
[0190] Figure 16 shows an example of the demagnetization curve of an unprocessed magnet using the GBE process. The squareness factor of FIG. 17 is better than that of FIG. 16, for example, which is processed using the BE process. 4 shows an example of a demagnetization curve for a magnet with improved temperature stability as indicated by the curve at 25°C. As shown in FIG. 16, the coercive force of the starting material is 1000-1100 kA / m, and as shown in FIG. As shown in FIG. 17, the final magnet has a coercive force of 1800-1900 kA / m. The change in content from the magnets whose properties are shown in FIG. 16, for example, from 0.4 wt. % Dy to 3.4 wt. % of the Dy is due to the rare earth additive material. The content of Nd, Co, or two or more of these is G It may be higher in magnets fabricated using the BE process.
[0191] Example 6 In some implementations, the system performs grain boundary engineering on scrap material. The scrap material has grain boundaries, NdFe 14 B1 matrix phase, or both, contain a large amount of Dy. The bulk of the Dy may be used to improve the magnetic properties of the final magnetic product made from the scrap material. Residual magnetism in the final magnetic product made from scrap materials can contribute to reduced performance. To increase (Br), the system replaces Dy with Fe in the scrap. The Dy may be removed from the material, for example, the system may pump Fe into the scrap material. The system may extrude Dy from the scrap material by feeding the scrap material through a Using Fe in an additive material that is mixed with the clap material, e.g. Dy may be removed from the scrap material.
[0192] The system may mix an additive material that does not contain any Dy with the scrap material. The additive materials are Fe, Nd, Co, or any combination of two of these in significant amounts, as shown in Table 9 below. For example, the system may include a system that ensures high magnetic performance of the final magnetic product. In order to achieve this, Fe is added to the scrap material, Dy is removed from the scrap material, or Do both and use Nd2Fe as much as possible. 14 For example, the system may be Adding Fe to scrap material, removing Dy from scrap material, or both to remove residual The magnetism (Br) may be increased and the coercivity (iHc) may be decreased.
[0193] Table 9 shows the two starting scrap materials s1 and s2, the additive material a, and the The amount of the final magnetic product f made from the feed and additive materials is expressed as a percentage by weight. For example, In Table 9 below, s1(e) is the amount of element e in the first starting scrap material s1, expressed as a percentage by weight. s2(e) is the amount of element e in the second starting scrap material s2, expressed in weight percent. In Table 9 below, the amount of element e in additive material a in weight percent is expressed as a(e ) and the amount of element e in the final magnetic product f in weight percent is represented as f(e). .
[0194] For clarity, some minor elements have been omitted from Table 9. The amounts in Table 9 are: The error is ±0.01~0.08wt% (due to ICP reading). [Table 9]
[0195] In the example shown in Table 9, the system may, for example, for each element e in the final magnetic product f: So, f(e) = 40wt% × s1(e) + 40wt% × s2(e) + 20wt% × a(e), and x s1 + 40wt% x s2 + 20wt% x a to mix the final magnetic product. For example, the system is g of s1, 40 kg of s2, and 20 kg of a were mixed to produce 100 kg of final magnetic product f.
[0196] Table 10 shows the magnetic properties of the two starting materials s1 and s2, and the final magnetic product f. 10 is a process in which 40 wt% x s1 is mixed with 40 wt% x s2 and 20 wt% x a to produce the final magnetic product f. The stem may improve the performance of the final magnetic product f compared to one or both of the two starting materials. For example, the system shows an increase in remanence (Br), energy product (BHmax) , decreasing the average coercivity (iHc), or two or more of these. [Table 10]
[0197] In some implementations, the GBE method comprises adding one or more of the compositions or methods described herein. In another embodiment, the method provides for the addition of 0.1 to 19 wt % of the rare earth element additive of the present invention. About 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5wt%, about 1wt%, about 2wt%, about 3wt%, about 4wt%, about 5wt%, about 6wt%, about 7wt%, about 8wt% , about 9wt%, about 10wt%, about 11wt%, about 12wt%, about 13wt%, about 14wt%, about 15wt%, about 16wt% , about 17 wt%, about 18 wt%, or about 19 wt% of one or more elements added or a combination of one or more elements added In yet another aspect, the method provides for the addition of a composition or method as described herein. to, about 0.1-0.5wt%, about 0.1-1wt%, about 0.5-1wt%, about 1-2wt%, about 1-3wt%, about 1-5 wt%, approx. 1~8wt%, approx. 1~12wt%, approx. 1~15wt%, approx. 1~19wt%, approx. 2~4wt%, approx. 2~6wt% , about 2 to 12 wt%, about 2 to 19 wt%, about 3 to 5 wt%, about 3 to 8 wt%, about 3 to 15 wt%, and about 3 to 19 wt% The present invention provides for the addition of one or more elemental additions or a combination of one or more elemental additions.
[0198] In some implementations, the initial sintered magnet block and, optionally, the additive material. The hydrogen mixing process is carried out under a hydrogen atmosphere at temperatures between 20 and 150°C and pressures between 1 and 60 bar (0.1 and 6 MPa). The initial sintered magnet block may be sintered in any suitable manner, to name a few. The water may be prepared using any suitable process or purchased from a commercial supplier. The powder resulting from the elementary mixing process is heated, preferably in situ, to 550-600°C to form the mixture. The mixture may be partially degassed. The average particle size in the powder resulting from the mixing process is 1. The average particle size can range from 1000 μm to 2000 mm. When a pressure of 50 bar (5 MPa) is used, The grain size is the grain size present in the original magnetic material, e.g., 2 to 8 μm, and the grain size is the grain size due to oxidation. The powder may correspond to particles in the range of 500 μm to 2000 mm that did not react with the acid. The coarse rare earth powder may be removed.
[0199] In some implementations, the hydrogen mixing process is performed until the particles are small enough for the final magnet. and employing pressures high enough to ensure that a jet milling operation can be omitted. In this example, larger particles are removed, thereby eliminating particles with higher oxygen concentrations. Sieving to remove the oxides can be advantageous. The sieving is carried out to ensure that the oxides are not part of the material recovered from the magnet. It constitutes the harder fraction of the material and is resistant to reduction to smaller particle sizes. This can be effective for:
[0200] Further mixing and homogenization of the magnetic powder mixture may be accomplished by using rollers to further homogenize the mixture. During roller milling, the milled material may be subjected to, for example, It may be lubricated with 1% Zn stearate. After the roller milling process, the magnetic powder The powder may be sieved to further remove any remaining rare earth oxides. wherein the sieving may be selective to remove particles larger than 500 μm. .
[0201] The lubricant used in roller milling may have a low oxygen content and / or Examples of lubricants include amides such as oleamide or amide; or other lower carbon-hydrogenate esters, or oleyl Examples of fatty acids include acetic acid.
[0202] The powder may be further homogenized by jet milling. The jet may be formed using air or an inert gas such as He, Ar, or N. The milling process homogenizes the mixture and further breaks down the individual grains into aggregates having a size of 1-4 μm. The reaction may be carried out for a time, e.g., 1 to 4 hours, and at a rate sufficient to break up the agglomerates. In some implementations, the jet milling process can be completed in 24 hours or less.
[0203] In some implementations, Nd-F compared to jet milling Nd-Fe-B elemental additives. An 80% reduction in jet milling time for eB powders has been observed. The particle size may be in the range of 4 to 10 μm. During the jet milling process, the agglomerates are While the oxidized rare earth powder can be broken down into individual particles, it can remain coarse and break down into larger particles, e.g. The oxidized rare earth coarse powder is removed to obtain the starting magnetic material. The amount of oxygen entrapped can be reduced, and more preferably suppressed, in the final magnet. This step involves the use of magnetic powder and (RE(TM) x ) Unused addition of elemental additives For the purpose of homogenizing the mixture with the additive materials, it is preferable to use a mixture that is completely free of oxygen contamination, e.g. This can be done under an inert atmosphere using Ar gas to break down individual grains segregated along grain boundaries. RE (rare earth) refers to any combination of Nd, Pr, Dy, Tb, Y, La, or Sm, and TM (transition element) refers to any combination of Nd, Pr, Dy, Tb, Y, La, or Sm. The additive material is any combination of Co, Ni, V, Nb, Mo, Ti, Zr, Al, Cu, Ga, or Fe. Point.
[0204] After the reduction, mixing and sieving of the particles is completed, the powder is aligned and pressed to form a hollow The compact may be formed in an air or inert atmosphere. Prior to pressing and alignment, a lubricant may be added to the powder. The powder may be pressed and aligned in a magnetic field. The green compact was then sintered at 1050-1100°C for 5 hours, followed by sintering at 900°C for 12 hours. The sintering temperature may be selected based on the hydrogenation / mixing temperature. Depends on the total rare earth addition added prior to processing.
[0205] In some implementations, it may be advantageous to use a mixture of raw material, e.g., from sintered magnets, and virgin raw material. Hydrogen blending may be used to facilitate homogenization with the additives. In a process suitable for rapid scalable fabrication, additional materials, e.g., rare earth oxides, can be added. Jet milling may be used for further homogenization with the ZnO or Nd / Pr. The implementation of this method includes milling, roller milling, high energy ball milling, rolling, and and other mixing steps.
[0206] In some implementations, the method includes adding 0.1 to 19 wt % of the composition or method described herein. In another embodiment, the method provides for the addition of one or more rare earth element additives in an amount of t%. About 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%, t%, about 1wt%, about 2wt%, about 3wt%, about 4wt%, about 5wt%, about 6wt%, about 7wt%, or about 8wt% The present invention provides the addition of one or more rare earth element additives or a combination of one or more rare earth element additives. In yet another aspect, the method includes adding about 0.1 to 0.5 wt. %, approximately 0.1~1wt%, approximately 0.5~1wt%, approximately 1~2wt%, approximately 1~3wt%, approximately 1~5wt%, approximately 1~8wt%, About 2-4 wt%, about 2-6 wt%, about 3-5 wt%, or about 3-8 wt% of one or more rare earth element additives or The addition of combinations of the above rare earth element additives is provided.
[0207] The above and other embodiments each optionally include one or more of the following features, either alone or in combination: The method may include performing the fragmentation and the mixing simultaneously. Fragmenting may include fragmenting the material to an average particle size of 1 to 4 μm. Fragmenting may include separating particles of a particle fraction having a size greater than the average size of the particles. The method may include removing particles of a size larger than the average size of the particles to obtain a low oxygen concentration. Removing the particles of the particle fraction to obtain a low oxygen concentration may include sieving.
[0208] In some implementations, the method further comprises: and mixing with another element selected from element additive A. The fragmentation step includes: Fragmenting to form a powder having an average particle size of about 1 micron to about 2 millimeters. The method may include further fragmenting the powder to an average particle size of about 1 to about 4 microns. The homogenization of the powder may include homogenizing the powder for about 1 hour. homogenizing the powder, which may have an average particle size of from about one micron to about two millimeters. and mixing the powder with a) the rare earth material R, and b) the elemental additive A to obtain the homogeneous powder. The method includes: a) dissolving the rare earth metal powder having an average particle size of about 1 to about 4 microns in the powder; and b) mixing said first and second materials R and said second and third material A with said elemental additive A to form said homogenous powder. The powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogenous powder. Producing includes forming the powder having an average particle size of about 1 micron to about 2 millimeters. a) mixing said rare earth material R and b) said elemental additive A to form said homogenous powder. and homogenizing the powder may include an average particle size of about 1 to about 4 microns. This may include homogenizing the powder.
[0209] In some implementations, the method further comprises: and fragmenting the powder to form said powder, said powder being further fragmented by: a) separating said rare earth material R and b) mixing said powder with said elemental additive A to produce said homogenous powder; a) mixing the fragmented rare earth material R and b) the fragmented elemental additive A to form the homogenous powder; The method may include generating a
[0210] In some implementations, the method includes sintering and magnetizing the homogenous powder to obtain a Nd-Fe- The homogenous powder may be sintered and magnetized to form a Nd—Fe—B magnetic product. forming the composite article comprises compacting the homogenous powder to form a green compact; The green compact is sintered at about 1000°C to about 1100°C, and the sintered green compact is heated to less than 15°C in an inert atmosphere. The method may include magnetizing the body to form the Nd—Fe—B magnetic article. Before magnetizing the sintered green compact, the sintered green compact is heat-treated at about 490°C to about 950°C. The method may include exposing the powder compact to an inert magnetic field at less than 15°C. The atomic percentage of Co in the Nd-Fe-B magnetic product may be 3% or less. The atomic percentage of Cu in the Nd-Fe-B magnetic product may be less than 0.3%. The combined atomic percentage of Nd, D and Co in the Nd-Fe-B magnetic product may be 77% or less. The total atomic percentage of y and Pr may be 18 at % or less. adding a lubricant to the powder prior to compacting the powder to form the green compact. The coercivity of the Nd-Fe-B magnetic article can be from about 0 to about 20% greater.
[0211] In some implementations, the method includes sintering and magnetizing the powder to obtain a magnetization ratio of at least 30%. forming a Nd-Fe-B magnetic article having increased final coercivity. The powder is sintered and magnetized to produce a Nd-Fe- B forming a magnetic product.
[0212] In some implementations, the method includes sintering and magnetizing the homogenous powder to form a substantially W a R b A c where W may include a Nd—Fe—B material and the subscripts a, b, and c represent the corresponding compositions or forming a Nd—Fe—B magnetic article having a composition of Nd—Fe—B (representing the atomic percentages of the elements) The powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogenous powder. Producing the powder includes uniformly distributing the rare earth material R and the elemental additive A. and sintering and magnetizing the homogeneous powder to form a Nd-Fe-B magnetic article. -First Nd2Fe in Fe-B magnetic products 14 The concentration of rare earth material R is increasing on average around the B phase. forming said Nd—Fe—B magnetic article having a concentration of elemental additive A and a concentration of said Nd—Fe—B magnetic article. The forming of the Nd-Fe-B magnetic article includes forming a plurality of Nd-Fe-B magnetic particles extending throughout the Nd-Fe-B magnetic article. In the grain boundary region of the grain, the concentration and element composition of the grain boundary phase are restored, modified, and improved on the average. and
[0213] In some implementations, mixing the powders comprises mixing the powders with: Pr, Nd, Dy, Co, Cu The element additive A may be mixed with at least three elements of pure Fe, Fe, or Fe. The elemental additive A may comprise pure Nd. The elemental additive A may comprise pure Pr. The method further comprises, prior to fragmentation, , which may include adding a lubricant to the powder.
[0214] The above and other embodiments each optionally include one or more of the following features, either alone or in combination: The Nd—Fe—B sintered magnet may be contained in an amount of less than about 0.1% and less than about 3%, respectively. and greater than about 27%, greater than about 60%, or greater than about 83% with a Br reduction of less than about 6%. The rare earth material R and the element additive A may exhibit an increase in iHc that is greater than or equal to the rare earth material R. The concentration of the element additive A and the concentration of the element additive R are the same as those of the initial NdFe in the Nd-Fe-B magnet. 14 B phase In the mixture of surrounding material W, the Nd-Fe-B sintered magnet is uniformly increased throughout the magnet. The atomic percent of the rare earth material R and the element additive A in the combination may be uniformly distributed. The fraction may be about 0.1 at% to about 19 at%. The Nd-Fe-B sintered magnet may be less than 5 microns. The Nd-Fe-B sintered magnet may have an average grain size of less than 2.5 microns. The Nd—Fe—B sintered magnet may have a weight of about 7.56 g / cm 3 ~Approx. 7.6g / cm 3 The density may include
[0215] In some implementations, the Nd—Fe—B sintered magnet contains Co at an atomic percentage of 3% or less. The Nd-Fe-B sintered magnet may contain Cu in an atomic percentage of 0.3% or less. The Nd-Fe-B sintered magnet may contain Fe and Co in a combined atomic percentage of 77% or less. The magnet may contain Nd, Dy, and Pr in a combined atomic percentage of 18% or less. may comprise pure Nd. The elemental additive A may comprise pure Pr.
[0216] The subject matter and functional operations described herein may be implemented in any manner that incorporates the structures disclosed herein. Digital electronic circuits, including structures and their structural equivalents, computers embodied in tangible objects computer software or firmware, computer hardware, or The embodiments of the subject matter described herein may be implemented in any combination of one or more of the following: , for execution by, or for controlling the operation of, a data processing apparatus; One or more computer programs encoded on a non-transitory program carrier The present invention may be implemented as a program, i.e., as one or more modules of computer program instructions. Alternatively, or in addition, the program instructions may be artificially generated and propagated signals. for transmission to a suitable receiver device for execution by a data processing device, A code on a machine-generated electrical, optical, or electromagnetic signal that is generated to encode information. The computer storage medium may be a machine-readable storage device, a machine-readable storage substrate, Random or serial access memory devices, or a combination of one or more of these could be.
[0217] The term "data processing device" refers to data processing hardware, e.g. a programmable A processor, computer, or multiple processors or computers capable of This includes apparatus, devices and machines for processing any kind of data. The device may be implemented using dedicated logic circuits, such as FPGAs (Field Programmable Gate Arrays) or ASICs. The device may also be, or may further include, an application specific integrated circuit (ASIC). In addition to the hardware, code that creates the environment in which a computer program runs, e.g. Processor firmware, protocol stack, database management system, operating Optionally, the code may comprise a processing system, a do.
[0218] A computer program is a program, software, or software application. Also referred to as an application, module, software module, script, or code. are sometimes written as such, but are compiled or interpreted languages, or written in any form of programming language, including declarative or procedural languages. The computer program can be implemented as a stand-alone program. or modules, components, subroutines, or computing environments The equipment may be deployed in any form, including as other units suitable for use in A computer program may correspond to a file in a file system. A program may, but is not required to, use other programs or data, e.g. in a single file dedicated to the program, or in multiple integrated files A file that stores, for example, one or more modules, subprograms, or pieces of code. It can be stored in a portion of a file that holds one or more scripts stored inside. A computer program is something that is located on one computer or at one site. or multiple computers distributed across multiple sites and interconnected by a communications network. The software can be deployed to run on a single computer.
[0219] The processes and logic flows described herein may be implemented using one or more computer programs. A program that executes one or more processes that perform a function by operating on input data and producing output. The processes and logic flows may be implemented by dedicated logic. Circuits, such as FPGAs (Field Programmable Gate Arrays) or ASICs (Application Specific Integrated Circuits) The present invention may also be implemented by special purpose logic circuits (integrated circuits), and the apparatus may be implemented as such special purpose logic circuits. It is also possible.
[0220] Examples of computers suitable for running a computer program include general purpose or A dedicated microprocessor, or both, or any other type of central processing unit may be used. Generally, the central processing unit stores instructions and data in a read-only memory, a random access memory, or a The essential elements of a computer are the ability to execute or carry out instructions. a central processing unit for executing the program, and one or more memory devices for storing instructions and data. Generally, a computer also has one or more mass storage devices for storing data. a magnetic, magneto-optical, or optical device, or Receiving data from the mass storage device; Transmitting data to the mass storage device , or both. Therefore, a computer does not necessarily have to have such a device. The computer can be connected to another device, such as a mobile phone, a personal digital assistant, to name a few. Personal digital assistants (PDAs), portable audio or video players, game consoles, global positioning systems GPS (Global Positioning System) receivers, or portable storage devices, such as those using Universal Serial Bus (U Serial SB) It can also be built into a flash drive.
[0221] A computer readable medium suitable for storing computer program instructions and data. Examples of such devices include semiconductor memory devices such as EPROM, EEPROM, and flash. memory devices; magnetic disks, e.g., internal hard disks or removable disks all forms of non-volatile storage, including disks; magneto-optical disks; and CD-ROM and DVD-ROM disks. The processor and memory include dedicated logic. The present invention may be supplemented by dedicated logic circuitry or may be incorporated in dedicated logic circuitry.
[0222] To provide for interaction with a user, embodiments of the subject matter described herein may include A display device for showing the image to the user, such as a CRT (cathode ray tube) or LCD (liquid crystal display) LCD monitor, as well as a display that allows the user to enter input into the computer A keyboard and a pointing device, such as a mouse or trackball, It may be implemented on a computer or other type of device to provide for user interaction. For example, the feedback provided to the user may be any form of sensory Feedback, e.g., visual feedback, auditory feedback, or tactile feedback and the input from the user can be acoustic input, voice input, or tactile input. In addition, the computer can receive the information from the user in any form, including by input. By sending and receiving documents to and from devices used by the User; for example, Responding to requests received from the web browser, the web page is sent to the web browser. By sending, it is possible to interact with the user.
[0223] Implementations of the subject matter described herein may be implemented, for example, as a backend, such as a data server. A computing system including a middleware component or A computing system including a server, such as an application server, or A client-end component, e.g., a user interface component, for implementing the subject matter described herein. Have a graphical user interface or web browser that allows you to talk A computing system including a client computer for performing One or more of the following components may be back-end, middleware, or front-end: The present invention can be implemented in a computing system having any combination of the above. A component may communicate through any form or medium of digital data communication, e.g., a communication network. An example of a communication network is a local area network (LON). Local Area Networks (LANs) and Wide Area Networks (WANs), such as the Internet. can be.
[0224] The computing system may include clients and servers. The server and the computer are usually remote from each other and typically interact through a communication network. The client and server relationship is that the two computers run on the same computer. It is created by a computer program that has a client-server relationship to the In some embodiments, the server may, for example, serve users acting as clients. Displaying data to a user interacting with the device and receiving user input from the user The data, e.g., an HTML page, is sent to the user device for reception. Data generated by the device, for example as a result of user interaction, is sent to the server. and can be received from the user device.
[0225] An example of this type of computer is shown in Figure 18. Figure 18 shows a typical computer system. 18 shows a schematic diagram of a system 1800. The system 1800, according to one implementation, may be implemented using the computer system previously described. The system may be used for the operations described in connection with any of the computer implementation methods. The system 1800 includes a processor 1810, a memory 1820, a storage device 1830, and an input / output device 1840. Each of the components 1810, 1820, 1830, and 1840 communicates with a system bus 1850. The processor 1810 processes instructions for execution within the system 1800. In one implementation, the processor 1810 is a single-threaded processor. In another implementation, the processor 1810 is a multi-threaded processor. The processor 1810 processes instructions stored in memory 1820 or on storage device 1830 to provide The input / output device 1840 may display graphic information for the user interface. can.
[0226] The memory 1820 stores information within the system 1800. In one implementation, the memory 1820 includes In one implementation, the memory 1820 is a volatile memory unit. In another implementation, the memory 1820 is a non-volatile memory unit.
[0227] The storage device 1830 may provide mass storage to the system 1800. The device 1830 is a computer-readable medium. In various different implementations, the storage device The 1830 is a floppy disk device, a hard disk device, an optical disk device, The device may be a hard disk drive, a USB stick, or a tape device.
[0228] The input / output device 1840 provides input / output operations to the system 1800. / Output device 1840 includes a keyboard and / or a pointing device. In the embodiment, the input / output device 1840 displays a graphical user interface. It is equipped with a display unit for
[0229] Although the specification contains many specific implementation details, these may not be included in the scope or claims of any invention. should not be construed as a limitation on the scope of what may be sought, but rather as a The description of features that may be specific to a particular embodiment of the present invention should be interpreted as a description of features that may be specific to a particular embodiment of the present invention. Certain features described herein in the context of embodiments may also be combined in a single embodiment. Conversely, various features that are described in the context of a single embodiment can also be implemented in multiple embodiments. The present invention may be practiced in several embodiments separately or in any suitable subcombination. Moreover, features may be described above as functioning in particular combinations; In some cases, claims may be filed as such initially, but in some cases, claims may be filed as follows: One or more features of a claimed combination may be deleted from the combination and the claimed combination may be modified in any manner. A combination may also cover a sub-combination or a variation of a sub-combination. do.
[0230] Similarly, although operations may be described in a particular order in the drawings, this is by no means intended to be limiting in any way as to how the desired results are achieved. In order to achieve this, it is not necessary that such operations be performed in the particular order shown, or in a sequential order. It should not be understood that the invention requires that all of the illustrated operations be performed. It should be understood that in certain circumstances, multitasking and parallel processing may be advantageous. Furthermore, the separation of the various system modules and components in the above embodiments is It should not be understood that such separation is necessary in all embodiments, and in general, The components and systems of the programs described herein may be integrated together into a single software product. It is understood that the present invention may be implemented in a variety of ways, including, but not limited to, the following aspects: It should be.
[0231] Certain embodiments of the subject matter have been described. Other embodiments are within the scope of the following claims. For example, the actions recited in the claims can be performed in a differing order, By way of example, the process depicted in the accompanying drawings may still achieve the desired results. The particular order illustrated, nor sequential order, is necessarily required to achieve the desired results. In some cases, multitasking and parallel processing can be advantageous.
[0232] The claims are as follows: The present application provides the following invention. (Configuration 1) A method for producing a Nd—Fe—B permanent magnet, comprising the steps of: melting the magnetic elements to produce a molten alloy; forming a cast alloy flake from the molten alloy, the cast alloy flake including a plurality of 2:14:1 phase grains; the cast alloy while maintaining at least a portion of the 2:14:1 phase grains from the cast alloy flake. grinding the flakes to form a first powder; pressing and aligning particles in the first powder to create a first compact; sintering the first compact to produce a sintered compact; While maintaining at least a portion of the 2:14:1 phase grains from the sintered compact, fragmenting the powder to form a second powder; and removing the second powder while maintaining at least a portion of the 2:14:1 phase grains from the second powder. a) a rare earth material R comprising at least one of i) Nd, ii) Pr, or iii) Dy; and b) i) Co, ii) Cu, or iii) Fe, and mixed with elemental additive A, which contains at least one of these additives, to form a homogeneous mixture. producing a powder; and sintering and magnetizing the homogenous powder to form a Nd-Fe-B magnetic article. method. (Configuration 2) forming the cast alloy flake from the molten alloy, the cast alloy flake including the plurality of 2:14:1 phase grains. forming cast alloy flakes from the molten alloy, each of the cast alloy flakes including a plurality of 2:14:1 phase grains. The method of claim 1, comprising: (Configuration 3) The rare earth material R and the elemental additive A are, as a whole, Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 F e 2.03 2. The method of claim 1, comprising at %. (Configuration 4) Fragmenting the sintered compact to an average particle size of 1 to 4 microns. 2. The method of claim 1, further comprising fragmenting the (Configuration 5) Fragmenting the sintered compact to form the second powder includes: removing particles having a particle fraction size greater than the average size of the particles in the second powder; and obtaining an oxygen concentration of less than 1.98 at% in the Nd-Fe-B magnetic product. How to. (Configuration 6) Fragmenting the sintered compact to form the second powder comprises fragmenting the sintered compact. pulverizing to form said second powder having an average particle size of about 1 micron to about 2 millimeters. 2. The method of claim 1, comprising: further fragmenting the second powder to an average particle size of about 1 to about 4 microns; and homogenizing the second powder; The method comprising: (Configuration 7) Homogenizing the second powder to an average particle size of about 1 micron to about 2 millimeters. homogenizing the second powder comprising: The second powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogenous forming a powder comprising: a) mixing the second powder having an average particle size of about 1 to about 4 microns with a a) said rare earth material R and b) said elemental additive A to form said homogenous powder. 7. The method according to claim 6. (Configuration 8) The second powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogeneous mixture. The powder may have an average particle size of about 1 micron to about 2 millimeters. mixing a second powder with a) the rare earth material R and b) the elemental additive A to form the homogenous powder; including causing; and Homogenizing the second powder produces a second powder having an average particle size of about 1 to about 4 microns. The method of claim 6, further comprising homogenizing the powder. (Configuration 9) Separately from fragmenting the sintered compact to form the second powder, the rare earth Fragmenting the material R and the elemental additive A; The second powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogenous powder. forming a second powder by dividing the second powder into a fraction of the rare earth material R and a fraction of the rare earth material R; 2. The method of claim 1, further comprising mixing the elemental additive A with the elemental additive B to form the homogenous powder. (Configuration 10) The method according to claim 1, wherein the atomic percentage of Co in the Nd-Fe-B magnetic product is 3.098 at% or less. Law. (Configuration 11) The method according to claim 1, wherein the atomic percentage of Cu in the Nd-Fe-B magnetic product is 0.1849 at% or less. Law. (Configuration 12) The combined atomic percentage of Fe and Co in the Nd-Fe-B magnetic product is about 76.3928 to about 83.1267a The method of claim 1, wherein the concentration is t%. (Configuration 13) The total atomic percentage of Fe and Co in the Nd-Fe-B magnetic product is 77 at% or less. The method described in Scheme 1. (Configuration 14) The total atomic percentage of Nd, Pr, and Dy in the Nd-Fe-B magnetic product is The method according to claim 1, wherein the combined atomic percentage of Nd, Pr, and Dy in (Configuration 15) The total atomic percentage of Nd, Dy, and Pr in the Nd-Fe-B magnetic product is 18 at% or less. The method of claim 1. (Configuration 16) The second powder is mixed with a) the rare earth material R and b) the elemental additive A to form the homogeneous mixture. forming a powder having a uniform distribution of the rare earth material R and the elemental additive A in the second powder; and sintering and magnetizing the homogenous powder to form the Nd—Fe—B magnetic article, The concentration of the rare earth material R increases surrounding the 2:14:1 phase grains in the Nd-Fe-B magnetic product. forming said Nd-Fe-B magnetic article having a concentration of said elemental additive A and a concentration of said elemental additive B. The method described in Scheme 1. (Configuration 17) The old Nd-rich grain boundary phase derived from the sintered compact and contained in the second powder is replaced with the rare earth 17. The method according to claim 16, further comprising replacing the grain boundary phase with a new grain boundary phase containing the material R and the elemental additive A. method. (Configuration 18) The Nd-Fe-B magnetic product comprises: Amount of Nd in the range [7.3635,11.1038] (at%, inclusive); Fe in the range [76.3928, 80.0287] (at%, inclusive); and B, a quantity in the range [5.7493,6.4244] (at%, inclusive), 2. The method of claim 1, comprising: (Configuration 19) The Nd-Fe-B magnetic product comprises: O in the range [0.09, 4.0] (at%, inclusive); and C, a quantity in the range [0.01, 1.0] (at%, inclusive), 20. The method of claim 18, comprising: (Configuration 20) The Nd-Fe-B magnetic product has an amount of D in the range of: [0.199, 4.0535] (at%, inclusive) 20. The method of claim 18, further comprising: y. (Configuration 21) The Nd-Fe-B magnetic product has an amount of P in the range of [1.445, 3.6323] (at%, inclusive). 20. The method of claim 18, further comprising: (Configuration 22) The Nd-Fe-B magnetic article contains Co in an amount ranging from: [0, 3.098] (at%, inclusive). 19. The method of claim 18. (Configuration 23) The Nd-Fe-B magnetic product is in an amount ranging from: [0.0508, 0.1849] (at%, inclusive) 20. The method of embodiment 18, further comprising Cu. (Configuration 24) The total amount of the rare earth material R in the Nd-Fe-B magnetic product is [12.66, 15.03] (at%, both ends 19. The method of claim 18, wherein the range of values is inclusive of the values of (Configuration 25) The rare earth material R is: i) With respect to the combination of the rare earth material R and the element additive material A, [6.1717, 11.8917] ( at%, inclusive) ii) [1.5495, 4.821] (at% , inclusive) or iii) [0.2132, 5.3753](at %, inclusive) of Dy, and The elemental additive A is: i) [0, 4.0948] (at%, both ends) for the combination of the rare earth material R and the element additive material A (including values of ii) [0.0545, 0.2445] (at% , inclusive) of Cu, or iii) With respect to the combination of the rare earth material R and the element additive material A, [81.1749, 85.867] (at %, inclusive) The method of claim 1, further comprising at least one of: (Configuration 26) Sintering and magnetizing the homogenous powder to form a Nd—Fe—B magnetic article. The powder is sintered and magnetized to obtain a sintered compact having a remanence and coercivity at least equal to that of the sintered compact. 2. The method of claim 1, comprising forming a Nd-Fe-B magnetic product. (Configuration 27) The coercive force of the Nd-Fe-B magnetic product is about 0 to about 20% greater than the coercive force of the sintered compact. 27. The method of claim 26. (Configuration 28) Sintering and magnetizing the homogenous powder to form a Nd—Fe—B magnetic article. The powder is sintered and magnetized to obtain a final remanence that is about 97% of the original remanence of the sintered compact. and said Nd- having a final coercivity at least 30% greater than the other coercivity of said sintered compact. 2. The method of claim 1, comprising forming an Fe-B magnetic product. (Configuration 29) Sintering and magnetizing the homogenous powder to form a Nd—Fe—B magnetic article. The powder is sintered and magnetized to obtain a final remanence that is about 95% of the original remanence of the sintered compact. and said Nd- having a final coercivity at least 80% greater than the other coercivity of said sintered compact. 2. The method of claim 1, comprising forming an Fe-B magnetic product. (Configuration 30) Sintering and magnetizing the homogenous powder to form a Nd—Fe—B magnetic article. The powder is sintered and magnetized to produce a final remanence that is approximately 5% greater than the other remanence of the sintered compact. and the Nd-Fe-B magnetic material has a final coercivity at least equal to another coercivity of the sintered compact. 2. The method of claim 1, further comprising forming a sexual product.
Claims
1. 1. A method of manufacturing a magnet, comprising the steps of: (a) Composite powder was mixed with stoichiometric Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 Compounds with atomic percent mixing with a composition comprising (b) sintering and magnetizing the mixture from step (a) to form a magnetic product; The method comprising:
2. melting the magnetic element to create a molten alloy; forming a cast alloy flake from the molten alloy, the cast alloy flake including a plurality of 2:14:1 phase grains; the cast alloy while maintaining at least a portion of the 2:14:1 phase grains from the cast alloy flake. grinding the flakes to form a first powder; Pressing the particles in the first powder to form a first compact and aligning the particles in a magnetic field. To do; sintering the first compact to produce a sintered compact; and While maintaining at least a portion of the 2:14:1 phase grains from the sintered compact, to form said composite powder; 2. The method of claim 1, further comprising:
3. Stoichiometric Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 The composition having an atomic percent of impurity As such, other incidental transition metals or rare earth metals, and (a)(i) less than 0.12 atomic percent oxygen (O); or (ii) 0.00009 to 0.18 atomic percent oxygen (O); and (b)(i) less than 0.0058 atomic percent carbon (C); or (ii) 0.0001 to 0.09 atomic percent carbon (C); 2. The method of claim 1, comprising:
4. Stoichiometric Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 said composition having an atomic percent of (a)Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 Atmo % and other incidental impurities a transition metal or rare earth metal, and (b)(i) less than 0.12 atomic percent oxygen (O); or (ii) 0.00009 to 0.18 atomic percent oxygen (O); and (c)(i) less than 0.0058 atomic percent carbon (C); or (ii) 0.0001 to 0.09 atomic percent carbon (C); 4. The method of claim 3, consisting essentially of:
5. Stoichiometric Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 said composition having an atomic percent of (a)Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 atomic percent, and other incidental transitions as impurities metal or rare earth metal, and (b)(i) less than 0.12 atomic percent oxygen (O); or (ii) 0.00009 to 0.18 atomic percent oxygen (O); and (c)(i) less than 0.0058 atomic percent carbon (C); or (ii) 0.0001 to 0.09 atomic percent carbon (C); 4. The method of claim 3, consisting essentially of:
6. Stoichiometric Nd 8.5-12.5 Dy 35-45 Co 32-41 Cu 3-6.5 Fe 1.5-5 said composition having an atomic percent of (a)Nd 11.92 Dy 42.32 Co 38.39 Cu 5.34 Fe 2.03 atomic percent, and other incidental transitions as impurities metal or rare earth metal, and (b)(i) less than 0.12 atomic percent oxygen (O); or (ii) 0.00009 to 0.18 atomic percent oxygen (O); and (c)(i) less than 0.0058 atomic percent carbon (C); or (ii) 0.0001 to 0.09 atomic percent carbon (C); 4. The method of claim 3, comprising:
7. The method according to any one of claims 1 to 6, wherein the magnetic product is a Nd-Fe-B permanent magnet.
8. The fragmentation of the sintered compact is performed by fragmenting the sintered compact into particles having a size in the range of 1 micrometer to 4 micrometers. The method of claim 2 , resulting in the composite powder having an average particle size.
9. The sintered compact is fragmented to form the composite powder, Removing particles having a particle fraction size greater than the average size of the particles in the composite powder 3. The method of claim 2, comprising:
10. The fragmenting of the sintered compact is performed by fragmenting the sintered compact into pieces having sizes ranging from about 1 micrometer to about 2 millimeters. The method of claim 2 , further comprising forming the composite powder having an average particle size.
11. The composite powder has an average particle size of about 1 micrometer to about 2 millimeters, The method is: The composite powder is mixed with a grain boundary additive composition to form a composite powder having an average particle size ranging from about 1 to about 4 micrometers. The method of claim 10, further comprising forming the composite powder having a size.
12. 8. The method of claim 7, wherein the atomic percentage of Co in the magnetic article is less than or equal to 3.098 atomic %.
13. 8. The method of claim 7, wherein the atomic percentage of Cu in the magnetic article is less than or equal to 0.1849 atomic %.
14. The combined atomic percentage of Fe and Co in the magnetic article is between about 76.3928 atomic % and about 83.1267 atomic %.
8. The method of claim 7, wherein the concentration is 0.01 to 0.1%.
15. 8. The magnetic article according to claim 7, wherein the combined atomic percentage of Fe and Co in the magnetic article is 77 atomic % or less. Method of posting.
16. The total atomic percentage of Nd, Pr, and Dy in the magnetic product is and Dy are each equal to or greater than the total atomic percentage; and the magnetic product is a Nd—Fe—B permanent magnet. The method according to claim 2.
17. The total atomic percentage of Nd, Dy, and Pr in the magnetic product is 18 atomic % or less. Item 7. The method described in item 7.
18. The old Nd-rich grain boundary phase derived from the sintered compact and contained in the composite powder is 3. The method of claim 2, further comprising replacing the grain boundary phase with a new grain boundary phase comprising the additive.
19. The magnetic product comprises: Nd in an amount in the range [7.3635, 11.1038] (atomic percent, inclusive); Fe in an amount in the range of [76.3928, 80.0287] (atomic percent, inclusive); and B in the range [5.7493, 6.4244] (atomic %, inclusive); 8. The method of claim 7, comprising:
20. The magnetic product comprises: O in an amount in the range [0.09, 4.0] (atomic %, inclusive); and C in an amount in the range [0.01, 1.0] (atomic %, inclusive); 20. The method of claim 19, comprising:
21. The magnetic article contains Dy in an amount in the range of [0.199, 4.0535] (atomic percent, inclusive).
20. The method of claim 19,
22. The magnetic article contains Pr in an amount in the range of [1.445, 3.6323] (atomic percent, inclusive).
20. The method of claim 19,
23. The magnetic article contains Cu in an amount in the range of [0.0508, 0.1849] (atomic percent, inclusive).
20. The method of claim 19,
24. The total amount of rare earth material R in the magnetic product is [12.66, 15.03] (atomic %, inclusive).
20. The method of claim 19, wherein the concentration of
25. Each of the sintered compact and the magnetic product exhibits remanence and coercivity, and the magnetic product the remanence and coercivity of the magnetic product are at least equal to those of the sintered compact; 3. The method of claim 2, wherein the magnet is an Fe—B permanent magnet.
26. 2. The magnetic product has a coercive force that is about 0 to about 20% greater than the coercive force of the sintered compact.
5. The method described in 5.
27. Each of the sintered compact and the magnetic product exhibits remanence and coercivity, and the magnetic product The residual magnetism of the magnetic product is about 97% of the residual magnetism of the sintered compact, and the coercive force of the magnetic product is the coercive force of said sintered compact is at least 30% greater; said magnetic product is a Nd-Fe-B permanent magnet; The method of claim 2.
28. Each of the sintered compact and the magnetic product exhibits remanence and coercivity, and the magnetic product The residual magnetism of the magnetic product is about 95% of the residual magnetism of the sintered compact, and the coercive force of the magnetic product is the coercive force of said sintered compact is at least 80% greater; said magnetic product is a Nd-Fe-B permanent magnet; The method of claim 2.
29. Each of the sintered compact and the magnetic product exhibits remanence and coercivity, and the magnetic product The residual magnetism of the magnetic product is about 5% greater than the residual magnetism of the sintered compact, and the coercive force of the magnetic product is is at least equal to the coercive force of the sintered compact; and the magnetic product is a Nd—Fe—B permanent magnet.
3. The method of claim 2.
Citation Information
Patent Citations
Method of manufacturing r-t-b-based sintered magnet
JP2013225533A
Cited By
Semiconductor device
CN122662239A